Glass ceramic and glass ceramic product

By designing microcrystalline glass containing SIO2, Al2O3, LI2O, Na2O, P2O5+ZRO2, etc., and through the process of crystalization and chemical enhancement, the existing glass mechanical performance has been solved, and the micro -crystal glass with high mechanical performance is achieved. Products.

CN119371107APending Publication Date: 2025-01-28CDGM OPTICAL GLASS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411558654.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-10-25
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Existing glasses are difficult to meet the demand for high mechanical properties during use, especially in applications of portable electronic devices.

Method used

By reasonable design of microcrystalline glass components, contain SIO2, Al2O3, LI2O, NA2O, P2O5+Zro2 and other ingredients, and form microcrystalline glass products with excellent mechanical properties through crystallizing process and chemical enhancement process.

Benefits of technology

The excellent mechanical properties of microcrystalline glass products are realized, and application needs in the fields of display equipment or electronic equipment are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005117270040000311
    Figure BDA0005117270040000311
  • Figure BDA0005117270040000321
    Figure BDA0005117270040000321
  • Figure BDA0005117270040000322
    Figure BDA0005117270040000322
Patent Text Reader

Abstract

The invention provides a microcrystalline glass product, which comprises the following components in percentage by weight: 41-60% of SiO2; 20 to 40 percent of Al2O3; li2O: 2%-15%; 3 to 20 percent of Na2O; the content of P2O5 + ZrO2 is 1 to 15 percent. Through reasonable component design, the obtained microcrystalline glass product has excellent mechanical properties, and can be applied to the fields of display equipment or electronic equipment and the like.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application for the invention patent application with application number 202211309432.1, application date October 25, 2022, and name “Microcrystalline glass, microcrystalline glass products and manufacturing methods thereof”. Technical Field

[0002] The present invention relates to a glass-ceramic, and in particular to a glass-ceramic with excellent mechanical properties, a glass-ceramic product and a manufacturing method thereof. Background Art

[0003] In recent years, with the continuous rise and development of consumer electronic products, glass, as a transparent and high-performance material, has been widely used in such electronic devices. For example, LED and LCD displays and computer monitors, portable electronic products (such as mobile phones, tablets and personal media terminals, etc.), the glass used in them not only needs to withstand the regular "touch" contact from the application for a long time, but also needs to withstand the accidental bending, scratches and impacts that may occur during use, which puts higher requirements on the relevant performance of the glass.

[0004] Glass-ceramics is a material that is formed by heat-treating the glass to precipitate crystals inside the glass. It has better mechanical properties than conventional glass. The microcrystals formed in the glass have obvious advantages over conventional glass in terms of bending resistance, wear resistance, and drop resistance. On the other hand, the mechanical properties of glass-ceramics can be further improved through chemical strengthening. Based on the above advantages, glass-ceramics or glass-ceramics products obtained after treatment are currently used in display devices or electronic devices with high requirements for drop resistance, pressure resistance, and scratch resistance, especially in the front and back covers of portable electronic devices (such as mobile phones, watches, PADs, etc.).

[0005] Therefore, developing a glass-ceramic and glass-ceramic product with excellent mechanical properties and suitable for display devices or electronic devices has become the goal pursued by scientific and technological personnel. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a microcrystalline glass and microcrystalline glass products with excellent mechanical properties.

[0007] The technical solution adopted by the present invention to solve the technical problem is:

[0008] (1) Glass-ceramic products, whose components, expressed in percentage by weight, contain: SiO 2 :40~60%;Al 2 O 3 :20~40%;Li 2 O: 2-15%; Na 2O: 3-20%; P 2 O 5 +ZrO 2 :1~15%.

[0009] (2) The glass-ceramic product according to (1), wherein the components, expressed in weight percentage, further contain: K 2 O: 0-8%; and / or ZnO: 0-6%; and / or B 2 O 3 : 0-6%; and / or RO: 0-8%; and / or TiO 2 :0~5%;and / or Ln 2 O 3 : 0-5%; and / or clarifier: 0-2%, wherein RO is one or more of MgO, CaO, SrO, BaO, Ln 2 O 3 For La 2 O 3 , Gd 2 O 3 , Y 2 O 3 One or more of .

[0010] (3) Glass-ceramic products, whose components are expressed by weight percentage, are SiO 2 :40~60%;Al 2 O 3 :20~40%;Li 2 O: 2-15%; Na 2 O: 3-20%; P 2 O 5 +ZrO 2 :1~15%; K 2 O: 0~8%; ZnO: 0~6%; B 2 O 3 :0~6%; RO: 0~8%; TiO 2 :0~5%;Ln 2 O 3 :0~5%; clarifier: 0~2%, the RO is one or more of MgO, CaO, SrO, BaO, Ln 2 O 3 For La 2 O 3 , Gd 2 O 3 , Y 2 O 3 One or more of .

[0011] (4) Glass-ceramic products, whose components contain SiO 2 、Al2 O 3 , Li 2 O and Na 2 O, the microcrystalline glass product contains a nepheline crystal phase, and the surface stress of the microcrystalline glass product is above 150 MPa.

[0012] (5) A glass-ceramic product, wherein the main crystal phase contains a nepheline crystal phase, and the Vickers hardness of the glass-ceramic product is 750 kgf / mm 2 above.

[0013] (6) Glass-ceramic products, the components of which are expressed in weight percentage, containing SiO 2 :40~60%;Al 2 O 3 :20~40%;Li 2 O: 2-15%; Na 2 O: 3-20%, the microcrystalline glass product contains nepheline crystal phase.

[0014] (7) Glass-ceramic products, whose components contain SiO 2 、Al 2 O 3 , Li 2 O and Na 2 O, the four-point bending strength of microcrystalline glass products with a thickness of less than 1 mm is above 700 MPa.

[0015] (8) Glass-ceramic products, whose components contain SiO 2 、Al 2 O 3 , Li 2 O and Na 2 O, the haze of microcrystalline glass products with a thickness of less than 1 mm is less than 0.15%.

[0016] (9) Microcrystalline glass products containing nepheline crystal phase, wherein the microcrystalline glass products with a thickness of less than 1 mm have a light transmittance of more than 88% at a wavelength of 550 nm.

[0017] (10) A microcrystalline glass product comprising a nepheline crystal phase, wherein the depth of the ion exchange layer of the microcrystalline glass product is greater than 50 μm.

[0018] (11) The glass-ceramic product according to any one of (4) to (10), wherein the components, expressed in weight percentage, include: SiO 2 : 40-60%; and / or Al 2 O 3 :20~40%;and / or Li 2 O: 2~15%; and / or Na 2 O: 3-20%; and / or P2 O 5 +ZrO 2 :1~15%.

[0019] (12) The glass-ceramic product according to any one of (4) to (11), wherein the components, expressed in weight percentage, further comprise: K 2 O: 0-8%; and / or ZnO: 0-6%; and / or B 2 O 3 : 0-6%; and / or RO: 0-8%; and / or TiO 2 :0~5%;and / or Ln 2 O 3 : 0-5%; and / or clarifier: 0-2%, wherein RO is one or more of MgO, CaO, SrO, BaO, Ln 2 O 3 For La 2 O 3 , Gd 2 O 3 , Y 2 O 3 One or more of .

[0020] (13) The glass-ceramic product according to any one of (1) to (12), wherein the components are expressed in weight percentage, wherein: (Al 2 O 3 +Na 2 O) / P 2 O 5 3.0 to 30.0, preferably (Al 2 O 3 +Na 2 O) / P 2 O 5 4.0 to 20.0, more preferably (Al 2 O 3 +Na 2 O) / P 2 O 5 is 5.0 to 15.0, and more preferably (Al 2 O 3 +Na 2 O) / P 2 O 5 It is 6.0~10.0.

[0021] (14) The glass-ceramic product according to any one of (1) to (13), wherein the components are expressed in weight percentage, wherein: SiO 2 / Al 2 O 3 1.2 to 2.8, preferably SiO 2 / Al2 O 3 1.3 to 2.5, more preferably SiO 2 / Al 2 O 3 is 1.5 to 2.2, and SiO is more preferred 2 / Al 2 O 3 It is 1.6~2.0.

[0022] (15) The glass-ceramic product according to any one of (1) to (14), wherein the components are expressed in weight percentage, wherein: SiO 2 / (Na 2 O+B 2 O 3 ) is 2.0 to 15.0, preferably SiO 2 / (Na 2 O+B 2 O 3 ) is 3.0 to 10.0, more preferably SiO 2 / (Na 2 O+B 2 O 3 ) is 4.0 to 8.0, and SiO 2 / (Na 2 O+B 2 O 3 ) is 5.0~7.0.

[0023] (16) The glass-ceramic product according to any one of (1) to (15), wherein the components are expressed in weight percentage, wherein: 2 O+Li 2 O) / SiO 2 0.1 to 0.8, preferably (Na 2 O+Li 2 O) / SiO 2 0.15 to 0.7, more preferably (Na 2 O+Li 2 O) / SiO 2 is 0.2 to 0.6, and more preferably (Na 2 O+Li 2 O) / SiO 2 It is 0.25~0.5.

[0024] (17) The glass-ceramic product according to any one of (1) to (16), wherein the components are expressed in weight percentage, wherein: (ZrO 2 +ZnO) / Na 2 O is 2.0 or less, preferably (ZrO 2 +ZnO) / Na 2O is 1.5 or less, and more preferably (ZrO 2 +ZnO) / Na 2 O is 0.01 to 1.0, and more preferably (ZrO 2 +ZnO) / Na 2 O is 0.1~0.5.

[0025] (18) The glass-ceramic product according to any one of (1) to (17), wherein the components are expressed in weight percentage, wherein: 2 O 5 +Na 2 O) / Li 2 O is 0.5 to 8.0, preferably (P 2 O 5 +Na 2 O) / Li 2 O is 0.8 to 5.0, more preferably (P 2 O 5 +Na 2 O) / Li 2 O is 1.0 to 3.0, and more preferably (P 2 O 5 +Na 2 O) / Li 2 O is 1.5~2.5.

[0026] (19) The glass-ceramic product according to any one of (1) to (18), wherein the components are expressed in weight percentage, wherein: K 2 O / ZrO 2 is 0.1 or more, preferably K 2 O / ZrO 2 0.2 to 10.0, more preferably K 2 O / ZrO 2 is 0.3 to 5.0, and K is more preferably 2 O / ZrO 2 It is 0.4~1.5.

[0027] (20) The glass-ceramic product according to any one of (1) to (19), wherein the components are expressed in weight percentage, wherein: (ZnO+RO+B 2 O 3 +TiO 2 ) / P 2 O 5 1.5 or less, preferably (ZnO+RO+B 2 O 3 +TiO 2 ) / P 2 O 5 is 1.0 or less, more preferably (ZnO+RO+B 2 O3 +TiO 2 ) / P 2 O 5 is 0.5 or less, and more preferably (ZnO+RO+B 2 O 3 +TiO 2 ) / P 2 O 5 is below 0.2, and the RO is one or more of MgO, CaO, SrO, and BaO.

[0028] (21) The glass-ceramic product according to any one of (1) to (20), wherein the components are expressed in weight percentage, wherein: SiO 2 : 43-55%, preferably SiO 2 : 46-53%; and / or Al 2 O 3 : 23-36%, preferably Al 2 O 3 :25.5~32%;and / or Li 2 O: 3-13%, preferably Li 2 O: 5.5~11%; and / or Na 2 O: 5-15%, preferably Na 2 O: 6.5-12%; and / or P 2 O 5 +ZrO 2 : 2-12%, preferably P 2 O 5 +ZrO 2 :4~10%;and / or K 2 O: 0-5%, preferably K 2 O: 0.1-3%; and / or ZnO: 0-3%, preferably ZnO: 0-1%; and / or B 2 O 3 : 0-3%, preferably B 2 O 3 : 0-1%; and / or RO: 0-5%, preferably RO: 0-2%; and / or TiO 2 : 0-3%, preferably TiO 2 :0~1%;and / or Ln 2 O 3 : 0-3%, preferably Ln 2 O 3 : 0-1%; and / or clarifier: 0-1%, preferably clarifier: 0-0.5%, the RO is one or more of MgO, CaO, SrO, BaO, Ln 2 O 3 For La 2 O 3, Gd 2 O 3 , Y 2 O 3 One or more of .

[0029] (22) The glass-ceramic product according to any one of (1) to (21), wherein the components are expressed in weight percentage, wherein: ZrO 2 : 0-6%, preferably ZrO 2 : 0-5%, more preferably ZrO 2 :0.1~3%;and / or P 2 O 5 : 0~10%, preferably P 2 O 5 : 1 to 8%, more preferably P 2 O 5 :2~6%.

[0030] (23) The glass-ceramic product according to any one of (1), (2), (4) to (12), further comprising, expressed in weight percentage: Yb 2 O 3 +Nb 2 O 5 +WO 3 +Bi 2 O 3 +Ta 2 O 5 +TeO 2 +GeO 2 : 0-5%, preferably Yb 2 O 3 +Nb 2 O 5 +WO 3 +Bi 2 O 3 +Ta 2 O 5 +TeO 2 +GeO 2 : 0-2%, more preferably Yb 2 O 3 +Nb 2 O 5 +WO 3 +Bi 2 O 3 +Ta 2 O 5 +TeO 2 +GeO 2 :0~1%.

[0031] (24) The glass-ceramic product according to any one of (1) to (23), wherein the composition does not contain SrO; and / or does not contain BaO; and / or does not contain MgO; and / or does not contain CaO; and / or does not contain ZnO; and / or does not contain PbO; and / or does not contain As 2 O 3 ; and / or does not contain TiO 2 ; and / or does not contain B 2 O 3 ; and / or does not contain Y 2 O 3 ; and / or does not contain La 2 O 3 ; and / or does not contain Gd 2 O 3 .

[0032] (25) According to any one of (1) to (24), the microcrystalline glass product contains a nepheline crystal phase; and / or a lithium silicate crystal phase; and / or a lithium phosphate crystal phase; and / or a petalite crystal phase; and / or a quartz crystal phase.

[0033] (26) According to any one of (1) to (25), the main crystal phase of the microcrystalline glass product is the nepheline crystal phase, or the microcrystalline glass product only contains the nepheline crystal phase.

[0034] (27) According to any one of the microcrystalline glass products described in (1) to (26), in the microcrystalline glass product, the weight percentage of the nepheline crystal phase in the microcrystalline glass product is 10 to 80%, preferably the weight percentage of the nepheline crystal phase in the microcrystalline glass product is 20 to 70%, and more preferably the weight percentage of the nepheline crystal phase in the microcrystalline glass product is 30 to 60%.

[0035] (28) The microcrystalline glass product according to any one of (1) to (27), wherein the ion exchange layer depth of the microcrystalline glass product is greater than 50 μm, preferably greater than 60 μm, more preferably greater than 80 μm, and further preferably greater than 100 μm; and / or the Vickers hardness is 750 kgf / mm 2 Above, preferably 780kgf / mm 2 More preferably 800kgf / mm 2 More preferably, 810 kgf / mm 2 and / or a grain size of 80 nm or less, preferably 60 nm or less, more preferably 50 nm or less, and further preferably 40 nm or less; and / or a surface stress of 150 MPa or more, preferably 170 MPa or more, and more preferably 190 MPa or more.

[0036] (29) The microcrystalline glass product according to any one of (1) to (28), for a microcrystalline glass product with a thickness of less than 1 mm, has a four-point bending strength of 700 MPa or more, preferably 750 MPa or more, and more preferably 800 MPa or more; and / or a drop ball test height of 1100 mm or more, preferably 1300 mm or more, and more preferably 1500 mm or more; and / or a haze of 0.15% or less, preferably 0.12% or less, and more preferably 0.10% or less; and / or a light transmittance of 550 nm is 88% or more, preferably 89% or more, more preferably 90% or more, and further preferably 91% or more; and / or an average optical |B| value of 400 to 800 nm is 1.5 or less, preferably 1.0 or less, and more preferably 0.8 or less.

[0037] (30) According to any one of (7) to (9) and (29), the thickness of the microcrystalline glass product is 0.2 to 1 mm, preferably 0.3 to 0.9 mm, more preferably 0.5 to 0.8 mm, and further preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm or 0.75 mm.

[0038] (31) The glass-ceramic product according to any one of (1), (2), (4) to (12), further comprising, expressed in weight percentage, 0 to 4% NiO; and / or Ni 2 O 3 : 0-4%; and / or CoO: 0-2%; and / or Co 2 O 3 :0~2%;and / or Fe 2 O 3 :0~7%;and / or MnO 2 :0~4%;and / or Er 2 O 3 :0~8%;and / or Nd 2 O 3 :0~8%;and / or Cu 2 O: 0-4%; and / or Pr 2 O 3 :0~8%;and / or CeO 2 :0~4%.

[0039] (32) Glass-ceramics, whose components, expressed in percentage by weight, contain: SiO 2 :40~60%;Al 2 O 3 :20~40%;Li 2 O: 2-15%; Na 2 O: 3-20%; P 2 O 5 +ZrO2 :1~15%.

[0040] (33) The glass-ceramics according to (32), wherein the components, expressed in weight percentage, further comprise: K 2 O: 0-8%; and / or ZnO: 0-6%; and / or B 2 O 3 : 0-6%; and / or RO: 0-8%; and / or TiO 2 :0~5%;and / or Ln 2 O 3 : 0-5%; and / or clarifier: 0-2%, wherein RO is one or more of MgO, CaO, SrO, BaO, Ln 2 O 3 For La 2 O 3 , Gd 2 O 3 , Y 2 O 3 One or more of .

[0041] (34) Glass-ceramics, whose components are expressed in weight percentage, are SiO 2 :40~60%;Al 2 O 3 :20~40%;Li 2 O: 2-15%; Na 2 O: 3-20%; P 2 O 5 +ZrO 2 :1~15%; K 2 O: 0~8%; ZnO: 0~6%; B 2 O 3 :0~6%; RO: 0~8%; TiO 2 :0~5%;Ln 2 O 3 :0~5%; clarifier: 0~2%, the RO is one or more of MgO, CaO, SrO, BaO, Ln 2 O 3 For La 2 O 3 , Gd 2 O 3 , Y 2 O 3 One or more of .

[0042] (35) Glass-ceramics, whose components contain SiO 2 、Al 2 O 3 , Li 2 O and Na2 O, the microcrystalline glass contains a nepheline crystal phase, and the Vickers hardness of the microcrystalline glass is 650kgf / mm 2 above.

[0043] (36) Glass-ceramics, whose main crystal phase contains nepheline crystal phase, and the Vickers hardness of the glass-ceramics is 650 kgf / mm 2 above.

[0044] (37) Glass-ceramics, whose components, expressed in weight percentage, contain SiO 2 :40~60%;Al 2 O 3 :20~40%;Li 2 O: 2-15%; Na 2 O: 3-20%, the microcrystalline glass contains nepheline crystal phase.

[0045] (38) Glass-ceramics, whose components contain SiO 2 、Al 2 O 3 , Li 2 O and Na 2 O, the main body of microcrystalline glass with a thickness of less than 1mm is dropped at a height of more than 1000mm.

[0046] (39) Glass-ceramics, whose components contain SiO 2 、Al 2 O 3 , Li 2 O and Na 2 O, the haze of microcrystalline glass with a thickness of 1 mm or less is 0.15% or less.

[0047] (40) Microcrystalline glass containing nepheline crystal phase, wherein the light transmittance of microcrystalline glass with a thickness of less than 1 mm at a wavelength of 550 nm is greater than 88%.

[0048] (41) Glass-ceramics, whose components contain SiO 2 、Al 2 O 3 , Li 2 O and Na 2 O. In the microcrystalline glass, the weight percentage of the nepheline crystal phase in the microcrystalline glass is 10 to 80%.

[0049] (42) The glass-ceramics according to any one of (35) to (41), wherein the components, expressed in weight percentage, include: SiO 2 : 40-60%; and / or Al 2 O 3 :20~40%;and / or Li 2 O: 2~15%; and / or Na2 O: 3-20%; and / or P 2 O 5 +ZrO 2 :1~15%.

[0050] (43) The glass-ceramics according to any one of (35) to (42), wherein the components, expressed in weight percentage, further comprise: K 2 O: 0-8%; and / or ZnO: 0-6%; and / or B 2 O 3 : 0-6%; and / or RO: 0-8%; and / or TiO 2 :0~5%;and / or Ln 2 O 3 : 0-5%; and / or clarifier: 0-2%, wherein RO is one or more of MgO, CaO, SrO, BaO, Ln 2 O 3 For La 2 O 3 , Gd 2 O 3 , Y 2 O 3 One or more of .

[0051] (44) The glass-ceramics according to any one of (32) to (43), wherein the components are expressed in weight percentage, wherein: (Al 2 O 3 +Na 2 O) / P 2 O 5 3.0 to 30.0, preferably (Al 2 O 3 +Na 2 O) / P 2 O 5 4.0 to 20.0, more preferably (Al 2 O 3 +Na 2 O) / P 2 O 5 is 5.0 to 15.0, and more preferably (Al 2 O 3 +Na 2 O) / P 2 O 5 It is 6.0~10.0.

[0052] (45) The glass-ceramic according to any one of (32) to (44), wherein the components are expressed in weight percentage, wherein: SiO 2 / Al 2 O 3 1.2 to 2.8, preferably SiO2 / Al 2 O 3 1.3 to 2.5, more preferably SiO 2 / Al 2 O 3 is 1.5 to 2.2, and SiO is more preferred 2 / Al 2 O 3 It is 1.6~2.0.

[0053] (46) The glass-ceramic according to any one of (32) to (45), wherein the components are expressed in weight percentage, wherein: SiO 2 / (Na 2 O+B 2 O 3 ) is 2.0 to 15.0, preferably SiO 2 / (Na 2 O+B 2 O 3 ) is 3.0 to 10.0, more preferably SiO 2 / (Na 2 O+B 2 O 3 ) is 4.0 to 8.0, and SiO 2 / (Na 2 O+B 2 O 3 ) is 5.0~7.0.

[0054] (47) The glass-ceramics according to any one of (32) to (46), wherein the components are expressed in weight percentage, wherein: (Na 2 O+Li 2 O) / SiO 2 0.1 to 0.8, preferably (Na 2 O+Li 2 O) / SiO 2 0.15 to 0.7, more preferably (Na 2 O+Li 2 O) / SiO 2 is 0.2 to 0.6, and more preferably (Na 2 O+Li 2 O) / SiO 2 It is 0.25~0.5.

[0055] (48) The glass-ceramic according to any one of (32) to (47), wherein the components are expressed in weight percentage, wherein: (ZrO 2 +ZnO) / Na 2 O is 2.0 or less, preferably (ZrO 2 +ZnO) / Na2 O is 1.5 or less, and more preferably (ZrO 2 +ZnO) / Na 2 O is 0.01 to 1.0, and more preferably (ZrO 2 +ZnO) / Na 2 O is 0.1~0.5.

[0056] (49) The glass-ceramics according to any one of (32) to (48), wherein the components are expressed in weight percentage, wherein: 2 O 5 +Na 2 O) / Li 2 O is 0.5 to 8.0, preferably (P 2 O 5 +Na 2 O) / Li 2 O is 0.8 to 5.0, more preferably (P 2 O 5 +Na 2 O) / Li 2 O is 1.0 to 3.0, and more preferably (P 2 O 5 +Na 2 O) / Li 2 O is 1.5~2.5.

[0057] (50) The glass-ceramics according to any one of (32) to (49), wherein the components are expressed in weight percentage, wherein: K 2 O / ZrO 2 is 0.1 or more, preferably K 2 O / ZrO 2 0.2 to 10.0, more preferably K 2 O / ZrO 2 is 0.3 to 5.0, and K is more preferably 2 O / ZrO 2 It is 0.4~1.5.

[0058] (51) The glass-ceramics according to any one of (32) to (50), wherein the components are expressed in weight percentage, wherein: (ZnO+RO+B 2 O 3 +TiO 2 ) / P 2 O 5 1.5 or less, preferably (ZnO+RO+B 2 O 3 +TiO 2 ) / P 2 O 5 is 1.0 or less, more preferably (ZnO+RO+B2 O 3 +TiO 2 ) / P 2 O 5 is 0.5 or less, and more preferably (ZnO+RO+B 2 O 3 +TiO 2 ) / P 2 O 5 is below 0.2, and the RO is one or more of MgO, CaO, SrO, and BaO.

[0059] (52) The glass-ceramic according to any one of (32) to (51), wherein the components are expressed in weight percentage, wherein: SiO 2 : 43-55%, preferably SiO 2 : 46-53%; and / or Al 2 O 3 : 23-36%, preferably Al 2 O 3 :25.5~32%;and / or Li 2 O: 3-13%, preferably Li 2 O: 5.5~11%; and / or Na 2 O: 5-15%, preferably Na 2 O: 6.5-12%; and / or P 2 O 5 +ZrO 2 : 2-12%, preferably P 2 O 5 +ZrO 2 :4~10%;and / or K 2 O: 0-5%, preferably K 2 O: 0.1-3%; and / or ZnO: 0-3%, preferably ZnO: 0-1%; and / or B 2 O 3 : 0-3%, preferably B 2 O 3 : 0-1%; and / or RO: 0-5%, preferably RO: 0-2%; and / or TiO 2 : 0-3%, preferably TiO 2 :0~1%;and / or Ln 2 O 3 : 0-3%, preferably Ln 2 O 3 : 0-1%; and / or clarifier: 0-1%, preferably clarifier: 0-0.5%, the RO is one or more of MgO, CaO, SrO, BaO, Ln 2 O 3 For La 2O 3 , Gd 2 O 3 , Y 2 O 3 One or more of .

[0060] (53) The glass-ceramic according to any one of (32) to (52), wherein the components are expressed in weight percentage, wherein: ZrO 2 : 0-6%, preferably ZrO 2 : 0-5%, more preferably ZrO 2 :0.1~3%;and / or P 2 O 5 : 0~10%, preferably P 2 O 5 : 1 to 8%, more preferably P 2 O 5 :2~6%.

[0061] (54) The glass-ceramics according to any one of (32), (33), (35) to (43), wherein the components, expressed in weight percentage, further contain: Yb 2 O 3 +Nb 2 O 5 +WO 3 +Bi 2 O 3 +Ta 2 O 5 +TeO 2 +GeO 2 : 0-5%, preferably Yb 2 O 3 +Nb 2 O 5 +WO 3 +Bi 2 O 3 +Ta 2 O 5 +TeO 2 +GeO 2 : 0-2%, more preferably Yb 2 O 3 +Nb 2 O 5 +WO 3 +Bi 2 O 3 +Ta 2 O 5 +TeO 2 +GeO 2 :0~1%.

[0062] (55) The glass-ceramic according to any one of (32) to (54), wherein the components do not contain SrO; and / or do not contain BaO; and / or do not contain MgO; and / or do not contain CaO; and / or do not contain ZnO; and / or do not contain PbO; and / or do not contain As 2 O 3 ; and / or does not contain TiO 2 ; and / or does not contain B 2 O 3 ; and / or does not contain Y 2 O 3 ; and / or does not contain La 2 O 3 ; and / or does not contain Gd 2 O 3 .

[0063] (56) According to any one of the microcrystalline glass described in (32) to (55), the microcrystalline glass contains a nepheline crystal phase; and / or a lithium silicate crystal phase; and / or a lithium phosphate crystal phase; and / or a petalite crystal phase; and / or a quartz crystal phase.

[0064] (57) According to any one of (32) to (56), the main crystal phase of the glass-ceramic is the nepheline crystal phase, or the glass-ceramic contains only the nepheline crystal phase.

[0065] (58) According to any one of the microcrystalline glass described in (32) to (57), in the microcrystalline glass, the weight percentage of the nepheline crystal phase in the microcrystalline glass is 10 to 80%, preferably the weight percentage of the nepheline crystal phase in the microcrystalline glass is 20 to 70%, and more preferably the weight percentage of the nepheline crystal phase in the microcrystalline glass is 30 to 60%.

[0066] (59) The microcrystalline glass according to any one of (32) to (58), wherein the grain size of the microcrystalline glass is less than 80 nm, preferably less than 60 nm, more preferably less than 50 nm, and further preferably less than 40 nm; and / or the Vickers hardness is 650 kgf / mm 2 Above, preferably 680kgf / mm 2 More preferably 700kgf / mm 2 above.

[0067] (60) The microcrystalline glass according to any one of (32) to (59), for a microcrystalline glass with a thickness of less than 1 mm, has a body ball drop height of more than 1000 mm, preferably more than 1200 mm, and more preferably more than 1400 mm; and / or a haze of less than 0.15%, preferably less than 0.12%, and more preferably less than 0.10%; and / or a light transmittance of 550 nm wavelength is more than 88%, preferably more than 89%, more preferably more than 90%, and further preferably more than 91%; and / or an average optical |B| value of 400 to 800 nm is less than 1.5, preferably less than 1.0, and more preferably less than 0.8.

[0068] (61) According to any one of (38) to (40) and (60), the thickness of the microcrystalline glass is 0.2 to 1 mm, preferably 0.3 to 0.9 mm, more preferably 0.5 to 0.8 mm, and further preferably 0.55 mm or 0.6 mm or 0.68 mm or 0.7 mm or 0.75 mm.

[0069] (62) The glass-ceramics according to any one of (32), (33), (35) to (43), wherein the components, expressed in weight percentage, further contain: NiO: 0 to 4%; and / or Ni 2 O 3 : 0-4%; and / or CoO: 0-2%; and / or Co 2 O 3 :0~2%;and / or Fe 2 O 3 :0~7%;and / or MnO 2 :0~4%;and / or Er 2 O 3 :0~8%;and / or Nd 2 O 3 :0~8%;and / or Cu 2 O: 0-4%; and / or Pr 2 O 3 :0~8%;and / or CeO 2 :0~4%.

[0070] (63) Matrix glass, the components of which, expressed in weight percentage, contain: SiO 2 :40~60%;Al 2 O 3 :20~40%;Li 2 O: 2-15%; Na 2 O: 3-20%; P 2 O 5 +ZrO 2 :1~15%.

[0071] (64) The matrix glass according to (63), wherein the components, expressed in weight percentage, further contain: K 2 O: 0-8%; and / or ZnO: 0-6%; and / or B 2 O 3 : 0-6%; and / or RO: 0-8%; and / or TiO 2 :0~5%;and / or Ln 2 O 3 : 0-5%; and / or clarifier: 0-2%, wherein RO is one or more of MgO, CaO, SrO, BaO, Ln 2 O 3 For La 2 O 3 , Gd 2 O 3 , Y 2 O 3 One or more of .

[0072] (65) Matrix glass, the components of which are expressed in weight percentage, are SiO 2 :40~60%;Al 2 O 3 :20~40%;Li 2 O: 2-15%; Na 2 O: 3-20%; P 2 O 5 +ZrO 2 :1~15%; K 2 O: 0~8%; ZnO: 0~6%; B 2 O 3 :0~6%; RO: 0~8%; TiO 2 :0~5%;Ln 2 O 3 :0~5%; clarifier: 0~2%, the RO is one or more of MgO, CaO, SrO, BaO, Ln 2 O 3 For La 2 O 3 , Gd 2 O 3 , Y 2 O 3 One or more of .

[0073] (66) The matrix glass according to any one of (63) to (65), wherein the components are expressed in weight percentage, wherein: (Al 2 O 3 +Na 2 O) / P 2 O 53.0 to 30.0, preferably (Al 2 O 3 +Na 2 O) / P 2 O 5 4.0 to 20.0, more preferably (Al 2 O 3 +Na 2 O) / P 2 O 5 is 5.0 to 15.0, and more preferably (Al 2 O 3 +Na 2 O) / P 2 O 5 It is 6.0~10.0.

[0074] (67) The matrix glass according to any one of (63) to (66), wherein the components are expressed in weight percentage, wherein: SiO 2 / Al 2 O 3 1.2 to 2.8, preferably SiO 2 / Al 2 O 3 1.3 to 2.5, more preferably SiO 2 / Al 2 O 3 is 1.5 to 2.2, and SiO is more preferred 2 / Al 2 O 3 It is 1.6~2.0.

[0075] (68) The matrix glass according to any one of (63) to (67), wherein the components are expressed in weight percentage, wherein: SiO 2 / (Na 2 O+B 2 O 3 ) is 2.0 to 15.0, preferably SiO 2 / (Na 2 O+B 2 O 3 ) is 3.0 to 10.0, more preferably SiO 2 / (Na 2 O+B 2 O 3 ) is 4.0 to 8.0, and SiO 2 / (Na 2 O+B 2 O 3 ) is 5.0~7.0.

[0076] (69) The matrix glass according to any one of (63) to (68), wherein the components are expressed in weight percentage, wherein: (Na 2 O+Li 2 O) / SiO 2 0.1 to 0.8, preferably (Na 2 O+Li 2 O) / SiO 2 0.15 to 0.7, more preferably (Na 2 O+Li 2 O) / SiO 2 is 0.2 to 0.6, and more preferably (Na 2 O+Li 2 O) / SiO 2 It is 0.25~0.5.

[0077] (70) The matrix glass according to any one of (63) to (69), wherein the components are expressed in weight percentage, wherein: (ZrO 2 +ZnO) / Na 2 O is 2.0 or less, preferably (ZrO 2 +ZnO) / Na 2 O is 1.5 or less, and more preferably (ZrO 2 +ZnO) / Na 2 O is 0.01 to 1.0, and more preferably (ZrO 2 +ZnO) / Na 2 O is 0.1~0.5.

[0078] (71) The matrix glass according to any one of (63) to (70), wherein the components are expressed in weight percentage, wherein: 2 O 5 +Na 2 O) / Li 2 O is 0.5 to 8.0, preferably (P 2 O 5 +Na 2 O) / Li 2 O is 0.8 to 5.0, more preferably (P 2 O 5 +Na 2 O) / Li 2 O is 1.0 to 3.0, and more preferably (P 2 O 5 +Na 2 O) / Li 2 O is 1.5~2.5.

[0079] (72) The matrix glass according to any one of (63) to (71), wherein the components are expressed in weight percentage, wherein: K2 O / ZrO 2 is 0.1 or more, preferably K 2 O / ZrO 2 0.2 to 10.0, more preferably K 2 O / ZrO 2 is 0.3 to 5.0, and K is more preferably 2 O / ZrO 2 It is 0.4~1.5.

[0080] (73) The matrix glass according to any one of (63) to (72), wherein the components are expressed in weight percentage, wherein: (ZnO+RO+B 2 O 3 +TiO 2 ) / P 2 O 5 1.5 or less, preferably (ZnO+RO+B 2 O 3 +TiO 2 ) / P 2 O 5 is 1.0 or less, more preferably (ZnO+RO+B 2 O 3 +TiO 2 ) / P 2 O 5 is 0.5 or less, and more preferably (ZnO+RO+B 2 O 3 +TiO 2 ) / P 2 O 5 is below 0.2, and the RO is one or more of MgO, CaO, SrO, and BaO.

[0081] (74) The matrix glass according to any one of (63) to (73), wherein the components are expressed in weight percentage, wherein: SiO 2 : 43-55%, preferably SiO 2 : 46-53%; and / or Al 2 O 3 : 23-36%, preferably Al 2 O 3 :25.5~32%;and / or Li 2 O: 3-13%, preferably Li 2 O: 5.5~11%; and / or Na 2 O: 5-15%, preferably Na 2 O: 6.5-12%; and / or P 2 O 5 +ZrO 2 : 2-12%, preferably P2 O 5 +ZrO 2 :4~10%;and / or K 2 O: 0-5%, preferably K 2 O: 0.1-3%; and / or ZnO: 0-3%, preferably ZnO: 0-1%; and / or B 2 O 3 : 0-3%, preferably B 2 O 3 : 0-1%; and / or RO: 0-5%, preferably RO: 0-2%; and / or TiO 2 : 0-3%, preferably TiO 2 :0~1%;and / or Ln 2 O 3 : 0-3%, preferably Ln 2 O 3 : 0-1%; and / or clarifier: 0-1%, preferably clarifier: 0-0.5%, the RO is one or more of MgO, CaO, SrO, BaO, Ln 2 O 3 For La 2 O 3 , Gd 2 O 3 , Y 2 O 3 One or more of .

[0082] (75) The matrix glass according to any one of (63) to (74), wherein the components are expressed in weight percentage, wherein: ZrO 2 : 0-6%, preferably ZrO 2 : 0-5%, more preferably ZrO 2 :0.1~3%;and / or P 2 O 5 : 0~10%, preferably P 2 O 5 : 1-8%, more preferably P 2 O 5 :2~6%.

[0083] (76) The matrix glass according to (63) or (64), wherein the composition, expressed in weight percentage, further comprises: Yb 2 O 3 +Nb 2 O 5 +WO 3 +Bi 2 O 3 +Ta 2 O 5 +TeO 2 +GeO 2: 0-5%, preferably Yb 2 O 3 +Nb 2 O 5 +WO 3 +Bi 2 O 3 +Ta 2 O 5 +TeO 2 +GeO 2 : 0-2%, more preferably Yb 2 O 3 +Nb 2 O 5 +WO 3 +Bi 2 O 3 +Ta 2 O 5 +TeO 2 +GeO 2 :0~1%.

[0084] (77) The matrix glass according to any one of (63) to (65), wherein the composition does not contain SrO; and / or does not contain BaO; and / or does not contain MgO; and / or does not contain CaO; and / or does not contain ZnO; and / or does not contain PbO; and / or does not contain As 2 O 3 ; and / or does not contain TiO 2 ; and / or does not contain B 2 O 3 ; and / or does not contain Y 2 O 3 ; and / or does not contain La 2 O 3 ; and / or does not contain Gd 2 O 3 .

[0085] (78) The matrix glass according to (63) or (64), wherein the components, expressed in weight percentage, further contain: NiO: 0-4%; and / or Ni 2 O 3 : 0-4%; and / or CoO: 0-2%; and / or Co 2 O 3 :0~2%;and / or Fe 2 O 3 :0~7%;and / or MnO 2 :0~4%;and / or Er 2 O 3 :0~8%;and / or Nd 2 O 3 :0~8%;and / or Cu 2O: 0-4%; and / or Pr 2 O 3 :0~8%;and / or CeO 2 :0~4%.

[0086] (79) A microcrystalline glass molded body comprising the microcrystalline glass described in any one of (32) to (62).

[0087] (80) A glass cover plate comprising the microcrystalline glass product described in any one of (1) to (31), and / or the microcrystalline glass described in any one of (32) to (62), and / or the matrix glass described in any one of (63) to (78), and / or the microcrystalline glass formed body described in (79).

[0088] (81) A glass component comprising a microcrystalline glass product as described in any one of (1) to (31), and / or a microcrystalline glass as described in any one of (32) to (62), and / or a matrix glass as described in any one of (63) to (78), and / or a microcrystalline glass formed body as described in (79).

[0089] (82) A display device comprising the microcrystalline glass product described in any one of (1) to (31), and / or the microcrystalline glass described in any one of (32) to (62), and / or the matrix glass described in any one of (63) to (78), and / or the microcrystalline glass formed body described in (79), and / or the glass cover plate described in (80), and / or the glass component described in (81).

[0090] (83) An electronic device comprising the microcrystalline glass product described in any one of (1) to (31), and / or the microcrystalline glass described in any one of (32) to (62), and / or the matrix glass described in any one of (63) to (78), and / or the microcrystalline glass formed body described in (79), and / or the glass cover described in (80), and / or the glass component described in (81).

[0091] (84) According to any one of the methods for manufacturing microcrystalline glass products described in (1) to (31), the method comprises the following steps: forming a matrix glass, subjecting the matrix glass to a crystallization process to form a microcrystalline glass, and then subjecting the microcrystalline glass to a chemical strengthening process to form a microcrystalline glass product.

[0092] (85) According to the method for manufacturing microcrystalline glass products described in (84), the crystallization process includes the following steps: heating to a specified crystallization treatment temperature, maintaining the temperature for a certain period of time after reaching the crystallization treatment temperature, and then cooling down, the crystallization treatment temperature is 580-750°C, preferably 600-700°C, and the holding time at the crystallization treatment temperature is 0-8 hours, preferably 1-6 hours.

[0093] (86) According to the method for manufacturing a microcrystalline glass product described in (84), the crystallization process includes the following steps: performing a nucleation process at a first temperature, and then performing a crystal growth process at a second temperature higher than the nucleation process temperature.

[0094] (87) According to the method for manufacturing microcrystalline glass products described in (86), the crystallization process includes the following steps: the first temperature is 500-620°C, and the second temperature is 620-750°C; the holding time at the first temperature is 0-24 hours, preferably 2-15 hours; the holding time at the second temperature is 0-10 hours, preferably 0.5-6 hours.

[0095] (88) According to the method for manufacturing a microcrystalline glass product according to any one of (84) to (87), the chemical strengthening process includes: the microcrystalline glass is immersed in a salt bath of molten Na salt at a temperature of 350 to 470°C for 1 to 36 hours, preferably in the temperature range of 380 to 460°C, and the preferred time range is 2 to 10 hours; and / or the microcrystalline glass is immersed in a salt bath of molten K salt at a temperature of 360 to 450°C for 1 to 36 hours, preferably in the time range of 1 to 10 hours; and / or the microcrystalline glass is immersed in a mixed salt bath of molten K salt and Na salt at a temperature of 360 to 450°C for 1 to 36 hours, preferably in the time range of 2 to 24 hours.

[0096] (89) A method for manufacturing glass-ceramics according to any one of (32) to (62), comprising the steps of forming a matrix glass and then subjecting the matrix glass to a crystallization process to form glass-ceramics.

[0097] (90) According to the method for manufacturing microcrystalline glass described in (89), the crystallization process includes the following steps: heating to a specified crystallization treatment temperature, maintaining the temperature for a certain period of time after reaching the crystallization treatment temperature, and then cooling down, the crystallization treatment temperature is 580 to 750°C, preferably 600 to 700°C, and the holding time at the crystallization treatment temperature is 0 to 8 hours, preferably 1 to 6 hours.

[0098] (91) According to the method for manufacturing microcrystalline glass described in (89), the crystallization process includes the following steps: performing a nucleation process at a first temperature, and then performing a crystal growth process at a second temperature higher than the nucleation process temperature.

[0099] (92) According to the method for manufacturing microcrystalline glass described in (91), the crystallization process includes the following steps: the first temperature is 500-620°C, and the second temperature is 620-750°C; the holding time at the first temperature is 0-24 hours, preferably 2-15 hours; the holding time at the second temperature is 0-10 hours, preferably 0.5-6 hours.

[0100] (93) A method for manufacturing a microcrystalline glass molded body according to (79), the method comprising grinding or polishing the microcrystalline glass to form a microcrystalline glass molded body, or subjecting matrix glass or microcrystalline glass to a heat bending process or a press molding process at a certain temperature to form a microcrystalline glass molded body.

[0101] (94) According to the method for manufacturing a microcrystalline glass molded body described in (79), the method includes the following steps: subjecting the matrix glass to a crystallization heat treatment process, including heating, heat preservation for nucleation, heating, heat preservation for crystallization, and cooling to room temperature to form a pre-crystallized glass; and subjecting the pre-crystallized glass to heat processing and molding to obtain a microcrystalline glass molded body.

[0102] (95) The method for producing a glass-ceramic formed body according to (79), the method comprising the following steps:

[0103] 1) Heating and preheating: Place the matrix glass or pre-crystallized glass or microcrystalline glass in the mold. The mold passes through each heating station in the hot bending machine in turn and stays at each station for a certain period of time to keep warm. The temperature in the preheating zone is 400-800°C, the pressure is 0.01-0.05MPa, and the time is 40-200s;

[0104] 2) Pressurized molding: After preheating, the mold is transferred to the molding station. The hot bending machine applies a certain pressure to the mold. The pressure range is 0.1-0.8Mpa. The molding station temperature range is 650-850℃, and the molding time range is 40-200s.

[0105] 3) Maintaining pressure and cooling: The mold is transferred to the cooling station for cooling step by step. The cooling temperature range is 750-500°C, the pressure is 0.01-0.05Mpa, and the time is 40-200s.

[0106] The beneficial effect of the present invention is that through reasonable component design, the microcrystalline glass or microcrystalline glass products obtained by the present invention have excellent mechanical properties and meet the application requirements in the fields of display devices or electronic devices. DETAILED DESCRIPTION

[0107] The glass-ceramics and glass-ceramics products of the present invention are materials having a crystalline phase (sometimes also referred to as crystal) and a glass phase, which are different from amorphous solids. The crystalline phase of the glass-ceramics and glass-ceramics products can be identified by the peak angles appearing in the X-ray diffraction pattern of X-ray diffraction analysis and / or measured by TEMEDX.

[0108] After repeated experiments and studies, the inventors of the present invention obtained the microcrystalline glass or microcrystalline glass products of the present invention by regulating the content and content ratio of specific components constituting microcrystalline glass and microcrystalline glass products to specific values ​​and precipitating specific crystalline phases.

[0109] Next, the scope of each component (ingredient) of the matrix glass, microcrystalline glass and microcrystalline glass products of the present invention is described. In this specification, unless otherwise specified, the content of each component is expressed in weight percentage (wt%) relative to the total amount of matrix glass, microcrystalline glass or microcrystalline glass product material converted into oxide composition. Here, the "composition converted into oxide" means that when oxides, composite salts and hydroxides used as raw materials for the matrix glass, microcrystalline glass or microcrystalline glass product components of the present invention decompose and transform into oxides when melted, the total weight of the oxide material is taken as 100%. In addition, in this specification, when it is only referred to as glass, it is the matrix glass before crystallization (i.e., crystallization process treatment), the matrix glass after crystallization (i.e., crystallization process treatment) is called microcrystalline glass, and microcrystalline glass products refer to products obtained after chemical strengthening of microcrystalline glass.

[0110] Unless otherwise indicated in specific cases, the numerical ranges listed herein include upper and lower limits, and "above" and "below" include the endpoints, as well as all integers and fractions within the range, without limitation to the specific values ​​listed when defining the range. The term "about" as used herein means that the formula, parameters and other quantities and features are not and need not be exact, and may be approximate and / or larger or lower if necessary, reflecting tolerances, conversion factors and measurement errors, etc. "And / or" as used herein is inclusive, for example, "A; and / or B" means only A, or only B, or both A and B.

[0111] In some embodiments, the crystal phase of the glass-ceramic or glass-ceramic product of the present invention contains a nepheline crystal phase (including eucryptite and / or sodium nepheline), specifically, contains eucryptite, or contains sodium nepheline, or contains eucryptite and sodium nepheline at the same time. The glass-ceramic of the present invention may also contain other crystal phases besides the nepheline crystal phase, such as a lithium silicate crystal phase (one or both of lithium monosilicate and lithium disilicate); and / or a lithium phosphate crystal phase; and / or a petalite crystal phase; and / or a quartz crystal phase.

[0112] In some embodiments of the present invention, the crystal phase in the glass-ceramic or glass-ceramic products contains only nepheline crystal phase (one or both of eucryptite and sodium nepheline).

[0113] In some embodiments, when the microcrystalline glass or microcrystalline glass products contain nepheline crystal phase and other crystal phases, the main crystal phase of the microcrystalline glass or microcrystalline glass products is the nepheline crystal phase, that is, the nepheline crystal phase has a higher weight percentage than other crystal phases.

[0114] In some embodiments, the weight percentage of the nepheline crystal phase in the glass-ceramic or glass-ceramic product is 10-80%, preferably the weight percentage of the nepheline crystal phase in the glass-ceramic or glass-ceramic product is 20-70%, and more preferably the weight percentage of the nepheline crystal phase in the glass-ceramic or glass-ceramic product is 30-60%. In some embodiments, the weight percentage of the nepheline crystal phase in the glass-ceramic or glass-ceramic product is about 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, 101%, 10 1%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%.

[0115] SiO 2 It is the basic component of the matrix glass, glass-ceramics and glass-ceramics products of the present invention, and can be used to stabilize the network structure of glass and glass-ceramics. It is one of the components that form the nepheline crystal phase after crystallization. If SiO 2 When the content of SiO is below 40%, the crystals formed in the glass-ceramics will be less and the crystals will be coarser, which will affect the haze of the glass-ceramics and glass-ceramics products, as well as the drop ball test height of the glass-ceramics products. 2 The lower limit of the content is 40%, preferably 43%, and more preferably 46%. 2 When the content of SiO exceeds 60%, the glass melting temperature is high, clarification is difficult, and it is not easy to shape, which affects the consistency of the glass, the hot bending of the glass and microcrystalline glass, and is not conducive to the surface stress and ion exchange layer depth of microcrystalline glass products. 2The upper limit of the content is 60%, preferably 55%, and more preferably 53%. In some embodiments, the SiO2 content may be about 40%, 40.5%, 41%, 41.5%, 42%, 42.5%, 43%, 43.5%, 44%, 44.5%, 45%, 45.5%, 46%, 46.5%, 47%, 47.5%, 48%, 48.5%, 49%, 49.5%, 50%, 50.5%, 51%, 51.5%, 52%, 52.5%, 53%, 53.5%, 54%, 54.5%, 55%, 55.5%, 56%, 56.5%, 57%, 57.5%, 58%, 58.5%, 59%, 59.5%, 60% SiO2 2 .

[0116] Al 2 O 3 It is a component that forms the glass network structure. It is an important component that helps stabilize glass molding and improve chemical stability. It can also improve the mechanical properties of glass and increase the depth of the ion exchange layer and surface stress of microcrystalline glass products. 2 O 3 If the content is too high, the melting property and devitrification resistance of the glass will be reduced, and the crystals will tend to grow larger during crystallization, which will reduce the strength of the microcrystalline glass and microcrystalline glass products. 2 O 3 The content of Al is 20-40%, preferably 23-36%, and more preferably 25.5-32%. In some embodiments, the Al content may include about 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%, 25.5%, 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5%, 30%, 30.5%, 31%, 31.5%, 32%, 32.5%, 33%, 33.5%, 34%, 34.5%, 35%, 35.5%, 36%, 36.5%, 37%, 37.5%, 38%, 38.5%, 39%, 39.5%, 40% Al 2 O 3 .

[0117] In some embodiments, SiO 2 The content of Al 2 O 3 The ratio between the content of SiO 2 / Al 2 O 3 Controlling it within the range of 1.2 to 2.8 can improve the four-point bending strength of microcrystalline glass and microcrystalline glass products, and improve the light transmittance of microcrystalline glass and microcrystalline glass products. 2 / Al 2 O 3 1.2 to 2.8, more preferably SiO 2 / Al 2 O 3 is 1.3 to 2.5. Further, control SiO 2 / Al 2 O 3 In the range of 1.5 to 2.2, the |B| value of the glass-ceramics and the glass-ceramics products can be further reduced, and the surface stress of the glass-ceramics products can be increased. 2 / Al 2 O 3 1.5 to 2.2, more preferably SiO 2 / Al 2 O 3 In some embodiments, SiO 2 / Al 2 O 3 The value of can be 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, 1.55, 1.6, 1.65, 1.7, 1.75, 1.8, 1.85, 1.9, 1.95, 2.0, 2.05, 2.1, 2.15, 2.2, 2.25, 2.3, 2.35, 2.4, 2.45, 2.5, 2.55, 2.6, 2.65, 2.7, 2.75, 2.8.

[0118] Li 2 O can promote the melting of glass and reduce the melting temperature of glass. It can form eucryptite crystal phase after crystallization. It is also the main component that replaces sodium and potassium ions in the chemical strengthening process. It can increase the surface stress of microcrystalline glass products, help to improve the drop ball test height of microcrystalline glass products, and increase the dielectric constant of microcrystalline glass and microcrystalline glass products. On the other hand, if too much Li 2 O, it is easy to reduce the chemical stability of the glass and deteriorate the light transmittance of the microcrystalline glass and microcrystalline glass products. 2 The content of O is 2-15%, preferably 3-13%, and more preferably 5.5-11%. In some embodiments, about 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15% Li 2 O.

[0119] Na 2O can participate in the crystallization to form the sodium nepheline phase after crystallization, and can also participate in chemical strengthening and improve the melting property of the glass. 2 If the content of O is too high, it is easy to cause the precipitated grains to increase or the type of precipitated crystal phase to change during the crystallization process. 2 The content of O is 3-20%, preferably 5-15%, and more preferably 6.5-12%. In some embodiments, the Na content may be about 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%. 2 O.

[0120] In some embodiments, Na 2 O and Li 2 Total content of ONa 2 O+Li 2 O and SiO 2 The ratio between the contents of 2 O+Li 2 O) / SiO 2 Controlling it within the range of 0.1 to 0.8 is conducive to obtaining the desired crystalline content of the microcrystalline glass and microcrystalline glass products, while refining the grains and improving the hardness of the microcrystalline glass and microcrystalline glass products. 2 O+Li 2 O) / SiO 2 0.1 to 0.8, more preferably (Na 2 O+Li 2 O) / SiO 2 is 0.15 to 0.7. Further, control (Na 2 O+Li 2 O) / SiO 2 In the range of 0.2 to 0.6, the light transmittance of the microcrystalline glass and microcrystalline glass products can be further improved, and the haze can be optimized. 2 O+Li 2 O) / SiO 2 is 0.2 to 0.6, and more preferably (Na 2 O+Li 2 O) / SiO 2 In some embodiments, (Na 2 O+Li 2O) / SiO 2 The value of can be 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8.

[0121] K 2 O is an optional component that helps improve the low temperature melting property and formability of glass, but if it contains too much K 2 O, it is easy to reduce the chemical stability of the glass. 2 The content of O is 0-8%, preferably 0-5%, and more preferably 0.1-3%. In some embodiments, the K content may include about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%. 2 O.

[0122] P 2 O 5 It can form crystal nuclei in the glass, promote uniform crystal growth, and help improve the low-temperature melting property of the glass; however, if it contains too much P 2 O 5 , it is easy to reduce the devitrification resistance of the glass and cause glass phase separation, and the mechanical properties of the microcrystalline glass and microcrystalline glass products tend to deteriorate. 2 O 5 The content of P is 0-10%, preferably 1-8%, and more preferably 2-6%. In some embodiments, the P may include about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%. 2 O 5 .

[0123] In some embodiments, Al 2 O 3 and Na 2 Total content of OAl 2 O 3 +Na 2 O and P 2 O 5 The ratio between the contents of Al 2 O 3 +Na 2 O) / P 2 O 5Controlling it within the range of 3.0 to 30.0 is conducive to obtaining the desired crystalline content of the microcrystalline glass and microcrystalline glass products, and improving the Vickers hardness of the microcrystalline glass and microcrystalline glass products, and increasing the drop ball test height. 2 O 3 +Na 2 O) / P 2 O 5 3.0 to 30.0, more preferably (Al 2 O 3 +Na 2 O) / P 2 O 5 is 4.0 to 20.0. Further, control (Al 2 O 3 +Na 2 O) / P 2 O 5 In the range of 5.0 to 15.0, the four-point bending strength of the microcrystalline glass and the microcrystalline glass products can be further optimized, and the depth of the ion exchange layer of the microcrystalline glass products can be increased. 2 O 3 +Na 2 O) / P 2 O 5 5.0 to 15.0, more preferably (Al 2 O 3 +Na 2 O) / P 2 O 5 In some embodiments, (Al 2 O 3 +Na 2 O) / P 2 O 5 The value of can be 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0, 16.5, 17 .0, 17.5, 18.0, 18.5, 19.0, 19.5, 20.0, 20.5, 21.0, 21.5, 22.0, 22.5, 23.0, 23.5, 24.0, 24.5, 25.0, 25.5, 26.0, 26.5, 27.0, 27.5, 28.0, 28.5, 29.0, 29.5, 30.0.

[0124] In some embodiments, P 2 O 5 and Na2 Total content of O 2 O 5 +Na 2 O and Li 2 The ratio of the content of O 2 O 5 +Na 2 O) / Li 2 O is controlled within the range of 0.5 to 8.0, which is beneficial to increasing the drop ball test height of the microcrystalline glass and microcrystalline glass products and increasing the ion exchange layer depth of the microcrystalline glass products. 2 O 5 +Na 2 O) / Li 2 O is 0.5 to 8.0, more preferably (P 2 O 5 +Na 2 O) / Li 2 O is 0.8 to 5.0. Further, control (P 2 O 5 +Na 2 O) / Li 2 When O is within the range of 1.0 to 3.0, the hardness and |B| value of the glass-ceramic and glass-ceramic products can be further optimized. 2 O 5 +Na 2 O) / Li 2 O is 1.0 to 3.0, and more preferably (P 2 O 5 +Na 2 O) / Li 2 O is 1.5 to 2.5. In some embodiments, (P 2 O 5 +Na 2 O) / Li 2 The value of O can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0.

[0125] ZrO 2 It has the function of crystallization and precipitation to form crystal nuclei, and at the same time helps to improve the chemical stability of glass. Studies have found that ZrO 2It can also improve the stability of glass by significantly reducing glass devitrification and lowering the liquidus temperature during the melting process; however, if it contains too much ZrO 2 , the devitrification resistance of the glass is easily reduced, and the difficulty of controlling the glass crystallization process increases. Therefore, ZrO 2 The content of ZrO is 0-6%, preferably 0-5%, and more preferably 0.1-3%. In some embodiments, the ZrO may include about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%. 2 .

[0126] In some embodiments, K 2 O content and ZrO 2 The ratio K between the contents 2 O / ZrO 2 Controlling K above 0.1 is beneficial to grain refinement and reducing the haze and grain size of microcrystalline glass and microcrystalline glass products. 2 O / ZrO 2 is 0.1 or more, and more preferably K 2 O / ZrO 2 is 0.2~10.0. Further, control K 2 O / ZrO 2 In the range of 0.3 to 5.0, the light transmittance of the microcrystalline glass and microcrystalline glass products can be further optimized to prevent the ion exchange layer depth of the microcrystalline glass products from deteriorating. 2 O / ZrO 2 is 0.3 to 5.0, and K is further preferred 2 O / ZrO 2 In some embodiments, K 2 O / ZrO 2The value can be 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, 1.55, 1.6, 1.65, 1.7, 1.75, 1.8, 1.85, 1.9, 1.95, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0.

[0127] In some embodiments, P 2 O 5 and ZrO 2 Total content P 2 O 5 +ZrO 2 Controlling it within the range of 1 to 15% is conducive to grain refinement, reducing the grain size of microcrystalline glass and microcrystalline glass products, while reducing the |B| value of microcrystalline glass and microcrystalline glass products, and improving the light transmittance of microcrystalline glass and microcrystalline glass products. Therefore, P is preferred 2 O 5 +ZrO 2 1 to 15%, more preferably P 2 O 5 +ZrO 2 2 to 12%, more preferably P 2 O 5 +ZrO 2 In some embodiments, P 2 O 5 +ZrO 2 It can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%.

[0128] ZnO can improve the melting performance of glass, improve the chemical stability of glass, refine grains during crystallization, control the upper limit of ZnO content below 6%, and inhibit the reduction of devitrification resistance. Therefore, the ZnO content is 0-6%, preferably 0-3%, and more preferably 0-1%. In some embodiments, about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6% ZnO may be included.

[0129] In some embodiments, ZrO 2 The total content of ZrO and ZnO 2 +ZnO and Na 2 The ratio of O content (ZrO 2 +ZnO) / Na 2 O is controlled below 2.0, which is beneficial to reduce the haze and grain size of microcrystalline glass and microcrystalline glass products, and increase the drop ball test height of microcrystalline glass and microcrystalline glass products. 2 +ZnO) / Na 2 O is 2.0 or less, and more preferably (ZrO 2 +ZnO) / Na 2 O is 1.5 or less, and more preferably (ZrO 2 +ZnO) / Na 2 O is 0.01 to 1.0, and more preferably (ZrO 2 +ZnO) / Na 2 O is 0.1 to 0.5. In some embodiments, (ZrO 2 +ZnO) / Na 2 The value of O can be 0, greater than 0, 0.01, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, 1.55, 1.6, 1.65, 1.7, 1.75, 1.8, 1.85, 1.9, 1.95, 2.0.

[0130] B 2 O 3 It can improve the network structure of glass and adjust the chemical strengthening properties of microcrystalline glass. If its content is too high, it will be unfavorable for glass molding, and it will be easy to crystallize during molding, and the chemical stability will be reduced. 2 O 3The content of B is 0-6%, preferably 0-3%, and more preferably 0-1%. In some embodiments, the B may include about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%. 2 O 3 .

[0131] In some embodiments, SiO 2 The content of Na 2 O and B 2 O 3 Total content of Na 2 O+B 2 O 3 The ratio between SiO 2 / (Na 2 O+B 2 O 3 ) is controlled within the range of 2.0 to 15.0, which is beneficial to increasing the depth of the ion exchange layer of the microcrystalline glass product and improving the four-point bending strength of the microcrystalline glass and the microcrystalline glass product. 2 / (Na 2 O+B 2 O 3 ) is 2.0 to 15.0, more preferably SiO 2 / (Na 2 O+B 2 O 3 ) is 3.0 to 10.0. Further, control SiO 2 / (Na 2 O+B 2 O 3 ) is within the range of 4.0 to 8.0, the surface stress of the glass-ceramic product can be further optimized, and the drop ball test height of the glass-ceramic and the glass-ceramic product can be increased. 2 / (Na 2 O+B 2 O 3 ) is 4.0 to 8.0, and SiO 2 / (Na 2 O+B 2 O 3 ) is 5.0 to 7.0. In some embodiments, SiO 2 / (Na 2 O+B 2 O 3) can have a value of 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0.

[0132] Alkaline earth metal oxides RO (RO is one or more of MgO, CaO, SrO, and BaO) help to improve the devitrification resistance of glass and enhance the strength of glass; but when its content is high, the crystallization performance of glass is reduced, which is not conducive to obtaining the desired crystal phase type and grain size of microcrystalline glass. Therefore, the content of RO is 0 to 8%, preferably 0 to 5%, and more preferably 0 to 2%. In some embodiments, about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8% RO may be included.

[0133] TiO 2 It is an optional component that helps to lower the melting temperature of glass and improve chemical stability. The present invention contains less than 5% TiO 2 , which can make the crystallization process of glass easier to control, and TiO 2 The content of TiO is 3% or less, more preferably 1% or less. In some embodiments, it is further preferred that TiO 2 In some embodiments, the TiO may include about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%. 2 .

[0134] In some embodiments, ZnO, RO, B 2 O 3 、TiO 2 Total content of ZnO+RO+B 2 O 3 +TiO 2 With P 2 O 5 The ratio between the contents of ZnO+RO+B 2 O 3 +TiO 2 ) / P 2 O 5 Controlling below 1.5 is beneficial to reducing the haze of microcrystalline glass and microcrystalline glass products, improving light transmittance, and increasing the surface stress of microcrystalline glass products.2 O 3 +TiO 2 ) / P 2 O 5 1.5 or less, more preferably (ZnO+RO+B 2 O 3 +TiO 2 ) / P 2 O 5 is 1.0 or less, and more preferably (ZnO+RO+B 2 O 3 +TiO 2 ) / P 2 O 5 is 0.5 or less, and more preferably (ZnO+RO+B 2 O 3 +TiO 2 ) / P 2 O 5 In some embodiments, (ZnO+RO+B 2 O 3 +TiO 2 ) / P 2 O 5 The value of can be 0, greater than 0, 0.01, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1.0, 1.05, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5.

[0135] Ln 2 O 3 (Ln 2 O 3 For La 2 O 3 , Gd 2 O 3 , Y 2 O 3 One or more of these can reduce the difficulty of glass melting. Too much content will make it difficult to form crystals during glass crystallization, and the drop ball test height of microcrystalline glass and microcrystalline glass products will decrease. 2 O 3 The upper limit of the content is 5%, preferably 3%, and more preferably 1%. In some embodiments, about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% Ln may be included. 2 O3 .

[0136] In some embodiments, the matrix glass, glass-ceramic or glass-ceramic product may further contain 0-2% of a clarifier to improve the defoaming ability of the matrix glass, glass-ceramic or glass-ceramic product. Such a clarifier includes but is not limited to Sb 2 O 3 SnO 2 , SnO, F (fluorine), Cl (chlorine) and Br (bromine), preferably Sb 2 O 3 SnO 2 As the clarifier, Sb is more preferred. 2 O 3 As a clarifier. When the above clarifiers are present alone or in combination, the upper limit of the content is preferably 1%, and the more preferred upper limit is 0.5%. In some embodiments, the content of one or more of the above clarifiers is about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%.

[0137] Without affecting the properties of the matrix glass, glass-ceramics or glass-ceramics products of the present invention, other components not mentioned above may be appropriately contained, such as Yb 2 O 3 , Nb 2 O 5 , WO 3 、Bi 2 O 3 、 2 O 5 、TeO 2 ,GeO 2 However, in order to maintain the excellent performance of the matrix glass, glass-ceramics or glass-ceramics products of the present invention, Yb 2 O 3 , Nb 2 O 5 , WO 3 、Bi 2 O 3 、 2 O 5 、TeO 2 ,GeO 2 The individual or total content of is 5% or less, more preferably 2% or less, further preferably 1% or less, and further preferably no content is contained.

[0138] PbO and As 2 O3 As toxic substances, even a small amount of them does not meet the requirements of environmental protection. Therefore, in some embodiments of the present invention, it is preferred that PbO and As are not contained. 2 O 3 .

[0139] In some embodiments of the present invention, a colored matrix glass, glass-ceramic or glass-ceramic product can be prepared by containing a colorant, so that the matrix glass, glass-ceramic or glass-ceramic product can present different colors. Preferably, the colorant contains: NiO: 0-4%; and / or Ni 2 O 3 : 0-4%; and / or CoO: 0-2%; and / or Co 2 O 3 :0~2%;and / or Fe 2 O 3 :0~7%;and / or MnO 2 :0~4%;and / or Er 2 O 3 :0~8%;and / or Nd 2 O 3 :0~8%;and / or Cu 2 O: 0-4%; and / or Pr 2 O 5 :0~8%;and / or CeO 2 :0~4%. The weight percentage content of the colorant and its function are described as follows:

[0140] The brown or green matrix glass, glass-ceramic or glass-ceramic product prepared by the present invention uses NiO, Ni 2 O 3 or Pr 2 O 5 As colorants. NiO and Ni 2 O 3It is a colorant used to prepare brown or green matrix glass, microcrystalline glass or microcrystalline glass products. The two components can be used alone or in combination. Their respective contents are generally less than 4%, preferably less than 3%. If the content exceeds 4%, the colorant cannot be well dissolved in the matrix glass, microcrystalline glass or microcrystalline glass products. The lower limit of their respective contents is above 0.1%. If it is less than 0.1%, the color of the matrix glass, microcrystalline glass or microcrystalline glass products is not obvious. In some embodiments, the present invention may include about 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0% NiO or Ni 2 O 3 When used in combination, NiO and Ni 2 O 3 The total amount is generally less than 4%, and the lower limit of the total amount is above 0.1%. In some embodiments, about 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0% NiO and Ni 2 O 3 . Use Pr 2 O 5As a colorant for green matrix glass, microcrystalline glass or microcrystalline glass products, it is used alone, with a general content of less than 8%, preferably less than 6%, and its lower limit is above 0.4%. If it is less than 0.4%, the color of the matrix glass, microcrystalline glass or microcrystalline glass products will not be obvious. In some embodiments, the present invention may comprise about 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4%, 4.6%, 4.8%, 5.0%, 5.2%, 5.4%, 5.6%, 5.8%, 6.0%, 6.2%, 6.4%, 6.6%, 6.8%, 7.0%, 7.2%, 7.4%, 7.6%, 7.8%, 8.0% Pr 2 O 5 .

[0141] The blue matrix glass, glass-ceramic or glass-ceramic product prepared by the present invention uses CoO or Co 2 O 3 As colorants, the two colorant components can be used alone or in combination, and their respective contents are generally less than 2%, preferably less than 1.8%. If the content exceeds 2%, the colorant cannot be well dissolved in the matrix glass, microcrystalline glass or microcrystalline glass products. The lower limits of their respective contents are above 0.05%. If they are lower than 0.05%, the color of the matrix glass, microcrystalline glass or microcrystalline glass products is not obvious. In some embodiments, the CoO or CoO may contain about 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0% 2 O 3 When used in combination, CoO and Co 2 O 3 The total amount does not exceed 2%, and the lower limit of the total amount is above 0.05%. In some embodiments, about 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0% of CoO and Co may be included. 2 O 3 .

[0142] The yellow matrix glass, glass-ceramics or glass-ceramics products prepared by the present invention use Cu 2 O or CeO2 The two colorant components are used alone or in combination, and the lower limit of their respective content is above 0.5%. If it is less than 0.5%, the color of the matrix glass, microcrystalline glass or microcrystalline glass products is not obvious. 2 O is 4% or less, preferably 3% or less. If the content exceeds 4%, the matrix glass is easily crystallized. In some embodiments, about 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0% Cu may be included. 2 O. CeO alone 2 The content is generally below 4%, preferably below 3%. If the content exceeds 4%, the matrix glass, microcrystalline glass or microcrystalline glass product has poor gloss. In some embodiments, about 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0% CeO 2 . If two colorants are mixed, the total amount is generally less than 4%, and the lower limit of the total amount is above 0.5%. In some embodiments, about 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0% of CeO 2 and Cu 2 O.

[0143] The black or smoke-grey matrix glass, glass-ceramic or glass-ceramic product prepared by the present invention is prepared by using Fe 2 O 3 as a colorant; or use Fe 2 O3 and CoO as a colorant; or Fe 2 O 3 and Co 2 O 3 Two colorants mixed together; or use Fe 2 O 3 , CoO and NiO three kinds of mixed colorants; or use Fe 2 O 3 、Co 2 O 3 The colorants used in the preparation of black and smoky gray matrix glass, microcrystalline glass or microcrystalline glass products mainly use Fe 2 O 3 Coloring, the content is 7% or less, preferably 5% or less, and the lower limit of the content is above 0.2%. In some embodiments, it can contain about 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2 .0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0% Fe 2 O 3 CoO and Co 2 O 3 Absorbs visible light and can deepen the coloring of matrix glass, glass-ceramics or glass-ceramics products. It is generally related to Fe 2 O 3 When mixed, the content of each is less than 0.6%, and the lower limit is more than 0.2%. In some embodiments, about 0.2%, 0.3%, 0.4%, 0.5%, 0.6% of CoO and / or Co 2 O 3 NiO absorbs visible light and can deepen the coloring of the matrix glass, glass-ceramics or glass-ceramics products. Generally, when mixed, its content is less than 1%, and the lower limit of the total amount is more than 0.2%. In some embodiments, NiO may be included in an amount of about 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or 1.0%.

[0144] The purple matrix glass, glass-ceramics or glass-ceramics products prepared by the present invention use MnO 2As a colorant, the usage content is generally below 4%, preferably below 3%, and the lower limit of the content is above 0.1%. If it is lower than 0.1%, the color of the matrix glass, microcrystalline glass or microcrystalline glass products will not be obvious. In some embodiments, the MnO may include about 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4.0% MnO 2 .

[0145] The pink matrix glass, glass-ceramics or glass-ceramics products prepared by the present invention use Er 2 O 3 As a colorant, the content is generally below 8%, preferably below 6%. 2 O 3 The coloring efficiency is low. When the content exceeds 8%, the color of the matrix glass, microcrystalline glass or microcrystalline glass products cannot be further deepened, but the cost is increased. The lower limit of the content is above 0.4%. If it is lower than 0.4%, the color of the matrix glass, microcrystalline glass or microcrystalline glass products is not obvious. In some embodiments, the invention may contain about 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4%, 4.6%, 4.8%, 5.0%, 5.2%, 5.4%, 5.6%, 5.8%, 6.0%, 6.2%, 6.4%, 6.6%, 6.8%, 7.0%, 7.2%, 7.4%, 7.6%, 7.8%, 8.0% of Er 2 O 3 .

[0146] The purple-red matrix glass, glass-ceramics or glass-ceramics products prepared by the present invention use Nd 2 O 3 As a colorant, the content is generally below 8%, preferably below 6%. 2 O 3The coloring efficiency is low. Even if the content exceeds 8%, the color of the matrix glass, microcrystalline glass or microcrystalline glass products cannot be further deepened. Instead, the cost is increased. The lower limit of the content is above 0.4%. If it is lower than 0.4%, the color of the matrix glass, microcrystalline glass or microcrystalline glass products is not obvious. In some embodiments, the Nd content may be about 0.4%, 0.6%, 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4%, 4.6%, 4.8%, 5.0%, 5.2%, 5.4%, 5.6%, 5.8%, 6.0%, 6.2%, 6.4%, 6.6%, 6.8%, 7.0%, 7.2%, 7.4%, 7.6%, 7.8%, 8.0% Nd 2 O 3 .

[0147] The red matrix glass, glass-ceramic or glass-ceramic product prepared by the present invention uses Er 2 O 3 、Nd 2 O 3 and MnO 2 Mixed colorants, Er ions in glass absorb at 400-500nm, Mn ions absorb mainly at 500nm, and Nd ions absorb strongly at 580nm. The mixture of the three substances can prepare red matrix glass, microcrystalline glass or microcrystalline glass products. 2 O 3 and Nd 2 O 3 It is colored by rare earth, and its coloring ability is relatively weak. 2 O 3 The usage is within 6%, Nd 2 O 3 The usage is within 4%, MnO 2 The coloring is strong, the usage amount is within the range of 2%, and the lower limit of the total amount of mixed colorants used is above 0.9%.

[0148] The "does not contain" and "0%" recorded in this article mean that the compound, molecule or element is not intentionally added as a raw material to the matrix glass, microcrystalline glass or microcrystalline glass product of the present invention; however, as raw materials and / or equipment for producing matrix glass, microcrystalline glass or microcrystalline glass products, there will be certain impurities or components that are not intentionally added, which will be contained in small amounts or trace amounts in the final matrix glass, microcrystalline glass or microcrystalline glass product, and this situation is also within the scope of protection of the patent of this invention.

[0149] In some embodiments of the present invention, the crystal phase in the glass-ceramics and glass-ceramics products contains a nepheline crystal phase, which provides high strength for the glass-ceramics and glass-ceramics products of the present invention, and the drop ball test height and four-point bending strength of the glass-ceramics and glass-ceramics products become larger. In some embodiments, the glass-ceramics or glass-ceramics products contain a eucryptite crystal phase, in some embodiments, the glass-ceramics or glass-ceramics products contain a sodium nepheline crystal phase, and in some embodiments, the glass-ceramics or glass-ceramics products contain both eucryptite and sodium nepheline crystal phases. The glass-ceramics of the present invention have excellent chemical strengthening properties, and can also be processed into glass-ceramics products through a chemical strengthening process to obtain excellent mechanical strength. Through reasonable component design, the glass-ceramics and glass-ceramics products of the present invention can obtain a suitable grain size, so that the glass-ceramics and glass-ceramics products of the present invention have high strength. The glass-ceramics and glass-ceramics products in the present invention have a suitable content of crystal phases, so that the glass-ceramics and glass-ceramics products of the present invention have excellent mechanical properties.

[0150] The grain size and crystalline phase type in the glass-ceramics or glass-ceramics products of the present invention will affect the haze and light transmittance of the glass-ceramics or glass-ceramics products. In some embodiments, the haze of the glass-ceramics products or glass-ceramics with a thickness of less than 1 mm is less than 0.15%, preferably less than 0.12%, and more preferably less than 0.10%. In some embodiments, the grain size of the glass-ceramics products or glass-ceramics is less than 80 nm, preferably less than 60 nm, and more preferably less than 50 nm.

[0151] In some embodiments, the crystalline content and refractive index of the glass-ceramics or glass-ceramics products of the present invention affect the |B| value of the glass-ceramics or glass-ceramics products. When the glass-ceramics or glass-ceramics products are observed in the visible light range, they appear bluish or yellowish, affecting the optical properties of the product, which is indicated by the |B| value in LAB (chromaticity value of the color of the substance). The glass-ceramics or glass-ceramics products of the present invention present a low |B| value in the visible light range. In some embodiments, the average optical |B| value of the glass-ceramics products or glass-ceramics with a thickness of less than 1 mm at 400 to 800 nm is less than 1.5, preferably less than 1.0, and more preferably less than 0.8.

[0152] In some embodiments, the glass-ceramics or glass-ceramics products of the present invention exhibit high transparency in the visible light range (i.e., the glass-ceramics or glass-ceramics products are transparent). The glass-ceramics or glass-ceramics products exhibit high transmittance in the visible light range. In some preferred embodiments, the light transmittance of the glass-ceramics products or glass-ceramics with a thickness of less than 1 mm at 550 nm is preferably 88% or more, more preferably 89% or more, and even more preferably 90% or more.

[0153] In some embodiments, an antimicrobial component can be added to the matrix glass, glass-ceramic, or glass-ceramic article. The glass-ceramic or glass-ceramic article described herein can be used in applications such as kitchen or dining countertops where exposure to harmful bacteria is likely. The antimicrobial components contained in the matrix glass, glass-ceramic, or glass-ceramic article include, but are not limited to, Ag, AgO, Cu, CuO, Cu 2 In some embodiments, the content of the above antimicrobial components alone or in combination is 2% or less, preferably 1% or less.

[0154] The matrix glass, glass-ceramics and glass-ceramics products of the present invention can be produced and manufactured by the following methods:

[0155] Forming matrix glass: Mix the raw materials evenly according to the component ratio, put the uniform mixture into a platinum or quartz crucible, and melt it in an electric furnace or gas furnace at a temperature range of 1250-1650℃ for 5-24 hours according to the melting difficulty of the glass composition. After melting and stirring to make it uniform, it is cooled to an appropriate temperature and cast into a mold, and slowly cooled.

[0156] The matrix glass of the present invention can be formed by a well-known method.

[0157] The matrix glass of the present invention is subjected to crystallization treatment by a crystallization process after forming or after forming processing, and crystals are uniformly separated out inside the glass. The crystallization treatment can be carried out by one stage, or by two stages, and preferably by two stages. The treatment of the nucleation process is carried out at the first temperature, and then the treatment of the crystal growth process is carried out at the second temperature higher than the nucleation process temperature. The crystallization treatment carried out at the first temperature is called the first crystallization treatment, and the crystallization treatment carried out at the second temperature is called the second crystallization treatment.

[0158] In order to obtain the desired physical properties of glass-ceramics, the preferred crystallization process is:

[0159] The above-mentioned crystallization treatment is carried out in one stage, and the nucleation process and the crystal growth process can be carried out continuously. That is, the temperature is raised to a specified crystallization treatment temperature, and after reaching the crystallization treatment temperature, the temperature is maintained for a certain period of time, and then the temperature is lowered. The crystallization treatment temperature is preferably 580 to 750°C, and in order to precipitate the desired crystalline phase, it is more preferably 600 to 700°C. The holding time at the crystallization treatment temperature is preferably 0 to 8 hours, and more preferably 1 to 6 hours.

[0160] When the crystallization treatment is performed in two stages, the first temperature is preferably 500 to 620° C., and the second temperature is preferably 620 to 750° C. The holding time at the first temperature is preferably 0 to 24 hours, more preferably 2 to 15 hours. The holding time at the second temperature is preferably 0 to 10 hours, more preferably 0.5 to 6 hours.

[0161] The above-mentioned holding time of 0 hours means that the temperature starts to drop or rise again within less than 1 minute after reaching the temperature.

[0162] In some embodiments, the matrix glass or glass-ceramics described herein can be manufactured into a formed body by various processes, including but not limited to sheets, and the processes include but are not limited to slit drawing, float process, rolling and other processes for forming sheets known in the art. Alternatively, the matrix glass or glass-ceramics can be formed by float process or rolling process. The formed body of the present invention also includes lenses, prisms, etc.

[0163] The matrix glass or glass-ceramics of the present invention can be used to manufacture a glass molded body or a glass-ceramics molded body in the form of a sheet by grinding or polishing, but the method for manufacturing a glass molded body or a glass-ceramics molded body is not limited to these methods.

[0164] The matrix glass or glass-ceramics of the present invention can be prepared into glass molded bodies or glass-ceramics molded bodies of various shapes by heat bending or pressing at a certain temperature, but is not limited to these methods.

[0165] In some embodiments, a glass forming body or a glass-ceramic forming body can be formed by a heat bending process. The heat bending process is a process in which 2D or 2.5D glass or glass-ceramic is placed in a mold and a 3D curved glass forming body or glass-ceramic forming body is formed by sequentially performing steps including heating preheating, pressurizing, and cooling under pressure in a heat bending machine.

[0166] In some embodiments, the glass-ceramic forming body has a 2.5D or 3D configuration, i.e., the glass-ceramic forming body has a non-planar configuration. As used herein, "non-planar configuration" means that in a 2.5D or 3D shape, at least a portion of the glass-ceramic forming body extends outward or along an angle with a plane defined by the original, laid-out configuration of the 2D matrix glass. A 2.5D or 3D glass-ceramic forming body formed from a matrix glass may have one or more protrusions or curved portions.

[0167] In some embodiments, in combination with the growth of the crystal phase and the transformation of the crystal phase in the microcrystalline glass, the manufacturing method of the microcrystalline glass forming body is a hot bending process method. Specifically, the method includes pre-crystallization and hot working forming. The pre-crystallization described in the present invention is to form pre-crystallized glass by controlling the crystallization process of the matrix glass, and the crystallinity of the pre-crystallized glass does not reach the crystallinity required by the performance index of the target microcrystalline glass forming body. The pre-crystallized glass is then formed into a microcrystalline glass forming body through a hot working forming process.

[0168] In some embodiments, a method for manufacturing a glass-ceramic formed body comprises the following steps:

[0169] 1) subjecting the matrix glass to a crystallization heat treatment process, including heating, heat preservation nucleation, heating, heat preservation crystallization, and cooling to room temperature to form pre-crystallized glass;

[0170] 2) The pre-crystallized glass is heat-processed and formed into a microcrystalline glass formed body.

[0171] The crystallization heat treatment process of the present invention comprises: heating the matrix glass at a certain temperature T h and time t h Under the condition of nucleation, then at a certain temperature T c and time t c The crystallinity of the obtained pre-crystallized glass did not reach the crystallinity required by the performance index of the target microcrystalline glass-ceramic formed body. Using the XRD test data, the total content of the main crystalline phase in the crystallinity of the pre-crystallized glass was calculated by the Rietveld full spectrum fitting refinement method. c1 . The pre-crystallization of the present invention is a complete process in terms of the process, including a nucleation process, one, two or three or more crystallization processes, etc. It is a complete process of heating, heat preservation, heating again, heat preservation..., and then cooling to room temperature according to the process. Different from the primary crystallization, secondary crystallization... mentioned in some documents or patents, the present invention is actually only the first crystallization, the second crystallization... in a complete crystallization process, and the middle is continuous, and there is no process of heating up again after cooling to room temperature.

[0172] The hot working forming of the present invention refers to the hot working process forming the pre-crystallized glass under certain conditions of temperature, time, pressure, etc., and the hot working forming includes more than one hot working process, and the hot working process includes but is not limited to pressing, bending or drawing the pre-crystallized glass under certain conditions of temperature, time, pressure, etc. In the hot working forming process, sometimes a molded body with a complex shape cannot be completed by one hot working, and may need to be completed by multiple hot workings of more than two times.

[0173] In some embodiments, the method for manufacturing the glass-ceramic formed body is a hot bending process. Specifically, in some embodiments, the method for manufacturing the glass-ceramic formed body includes the following steps:

[0174] 1) Preheating: Place the matrix glass or pre-crystallized glass or microcrystalline glass in the mold, and the mold passes through each heating station in the heat bending machine in turn, and stays at each station for a certain period of time to keep warm. The temperature in the preheating zone is 400-800°C, the pressure is 0.01-0.05MPa, and the time is 40-200s. In some embodiments, for a heat bending machine with 5 preheating stations, the initial temperature rise is generally set to about 500°C, and the subsequent stations gradually increase the temperature. The temperature gradient between two adjacent stations gradually decreases from low temperature to high temperature, and the temperature difference between the last preheating station and the first molding station is within 20°C.

[0175] 2) Pressurized molding: After preheating, the mold is transferred to the molding station. The hot bending machine applies a certain pressure to the mold. The pressure range is 0.1-0.8Mpa. The pressure is determined according to factors such as glass thickness and curvature. The molding station temperature range is 650-850℃, and the molding time range is 40-200s.

[0176] 3) Maintaining pressure and cooling: The mold is transferred to the cooling station and cooled down step by step. The cooling temperature range is controlled at 750-500℃, the pressure is 0.01-0.05Mpa, and the time is 40-200s.

[0177] In addition to controlling the appearance quality of ordinary high-aluminum glass, the hot bending process of microcrystalline glass forming bodies also requires controlling the impact of crystal growth and development during the hot bending process on the performance of the microcrystalline glass. For example, 3D curved microcrystalline glass used for display devices or electronic equipment casings requires close attention to light transmittance, haze, |B| value and uniformity after hot bending.

[0178] The change in the crystalline phase before and after hot bending determines the uniformity of the size of the microcrystalline glass formed body, the possibility of mass production and cost control. The matrix glass and microcrystalline glass of the present invention have excellent thermal processing properties. After hot bending, the change in the crystalline phase content is less than 20%, preferably less than 15%, and further preferably less than 10%, which can ensure the uniformity of the haze and |B| value of the microcrystalline glass formed body obtained after hot bending.

[0179] The matrix glass, glass-ceramic, and glass-ceramic articles described herein can have any reasonably useful thickness.

[0180] In addition to improving mechanical properties by precipitating crystals, the microcrystalline glass of the present invention can also obtain more excellent mechanical properties by forming a compressive stress layer, thereby making microcrystalline glass products.

[0181] In some embodiments, the matrix glass or glass-ceramics can be processed into sheets, and / or shaped (such as punching, hot bending, etc.), polished and / or brushed after shaping, and then chemically strengthened through a chemical strengthening process to form a glass-ceramics product. In some embodiments, the glass-ceramics formed body can be chemically strengthened through a chemical strengthening process to form a glass-ceramics product.

[0182] The chemical strengthening described in the present invention is an ion exchange method. During the ion exchange process, smaller metal ions in the matrix glass or glass-ceramic or glass-ceramic formed body are replaced or "exchanged" by larger metal ions of the same valence state near the matrix glass or glass-ceramic or glass-ceramic formed body. The replacement of smaller ions with larger ions forms compressive stress on the surface of the matrix glass or glass-ceramic or glass-ceramic formed body and tensile stress inside.

[0183] In some embodiments, the metal ion is a monovalent alkali metal ion (e.g., Na + , K + , Rb + , Cs + The ion exchange is carried out by immersing the matrix glass or glass-ceramic or glass-ceramic body in a salt bath containing at least one molten salt of a larger metal ion, which is used to replace the smaller metal ions in the matrix glass or glass-ceramic or glass-ceramic body. Alternatively, other monovalent metal ions such as Ag + 、Tl + , Cu + The one or more ion exchange processes used to chemically strengthen the matrix glass or glass-ceramic or glass-ceramic forming body may include, but are not limited to, immersing it in a single salt bath, or immersing it in multiple salt baths of the same or different compositions with washing and / or annealing steps between immersions.

[0184] In some embodiments, the matrix glass or glass-ceramic or glass-ceramic forming body can be prepared by immersing in a molten Na salt (e.g., NaNO) at a temperature of about 350 to 470°C. 3 ) for about 1 to 36 hours for ion exchange, preferably in the temperature range of 380 to 460° C., and preferably in the time range of 2 to 10 hours. In this embodiment, Na ions replace part of the Li ions in the matrix glass or microcrystalline glass or microcrystalline glass-formed body, thereby forming a surface compression layer and exhibiting high mechanical properties. In some embodiments, the matrix glass or microcrystalline glass or microcrystalline glass-formed body can be melted by immersing in a K salt (such as KNO) at a temperature of about 360 to 450° C. 3) for 1 to 36 hours for ion exchange, preferably for a time range of 1 to 10 hours. In some embodiments, the matrix glass or microcrystalline glass or microcrystalline glass-formed body can be ion exchanged by immersing in a mixed salt bath of molten K salt and Na salt at a temperature of about 360 to 450° C. for 1 to 36 hours, preferably for a time range of 2 to 24 hours.

[0185] The performance indicators of the glass-ceramics or glass-ceramics products of the present invention are tested by the following methods:

[0186] [Haze]

[0187] The spectrophotometer Minolta CM-3600A was used to prepare samples with a diameter of less than 1 mm and the test was carried out according to the GB2410-80 standard.

[0188] [Grain size]

[0189] Using a SEM scanning electron microscope, the microcrystalline glass is surface treated in HF acid, gold is sprayed on the surface of the microcrystalline glass, and the surface is scanned under the SEM scanning electron microscope to determine the size of its grains.

[0190] [Light transmittance]

[0191] The light transmittances described in this article are all external transmittances, sometimes referred to as transmittance.

[0192] The samples were processed to a thickness of less than 1 mm and polished in parallel with the opposite surfaces. The light transmittance at 550 nm was measured using a Minolta CM-3600A spectrophotometer.

[0193] [Surface stress] and [Ion exchange layer depth]

[0194] The surface stress was measured using a glass surface stress meter SLP-2000.

[0195] The depth of the ion exchange layer was measured using a glass surface stress meter SLP-2000.

[0196] The calculation was performed under the measurement conditions that the refractive index of the sample was 1.56 and the photoelastic constant was 24.5 [(nm / cm) / Mpa].

[0197] [Drop ball test height]

[0198] A sample of a microcrystalline glass product with a length and width of 150mm×73mm and a thickness of less than 1mm is placed on a glass supporting fixture, and a 132g steel ball is dropped from a specified height. The maximum drop ball test height that the sample can withstand without breaking is the impact. Specifically, the test is implemented starting from a drop ball test height of 400mm. Without breaking, the height is changed in sequence through 400mm, 500mm, 600mm, 700mm and above, with an interval of 100mm each time. For the embodiments with a "drop ball test height", microcrystalline glass products are used as test objects. The test data recorded as 1600mm in the embodiment indicates that the sample has withstood an impact of 1500mm and has not broken. When it was raised to 1600mm for testing, it broke. Therefore, the drop ball test height is 1600mm. The drop ball test height in the present invention is sometimes referred to as the drop ball height.

[0199] [Body falling ball height]

[0200] Place a microcrystalline glass sample with a length and width of 150mm×73mm and a thickness of less than 1mm on a glass supporting fixture, and drop a 32g steel ball from a specified height. The maximum drop ball test height that the sample can withstand without breaking is the main body drop ball height. Specifically, the test starts from a drop ball test height of 400mm. Without breaking, the height is changed in sequence through 400mm, 500mm, 600mm, 700mm and above, with an interval of 100mm each time. For the embodiments with a "main body drop ball height", microcrystalline glass is used as the test object, which is the drop ball test height of microcrystalline glass. The test data recorded as 1300mm in the embodiment indicates that the sample has withstood an impact of 1200mm without breaking, and it broke when it was raised to 1300mm for the test, so the main body drop ball height is 1300mm.

[0201] [Four-point bending strength]

[0202] The microcomputer-controlled electronic universal testing machine CMT6502 was used, the sample specification was less than 1 mm thick, and the test was performed according to ASTM C158-2002. In the present invention, the four-point bending strength is sometimes referred to as the bending strength.

[0203] [Vickers hardness]

[0204] The load when a diamond square pyramid indenter with an angle of 136° between the opposite faces is pressed into a pyramid-shaped depression on the test surface divided by the surface area (mm) calculated by the length of the depression. 2 ) value. The test load was 200 g and the holding time was 20 seconds. In the present invention, Vickers hardness may be simply referred to as hardness.

[0205] [|B|value]

[0206] Use Minolta CM-700d to test the B value. The sample specification is less than 1mm thick. Use the matching calibration long tube and short tube to perform instrument zero calibration and white plate calibration respectively. After calibration, use the long tube to perform air test again to determine the stability and calibration reliability of the instrument (B≤0.05). After the instrument is calibrated, place the product on the zero long tube for testing.

[0207] The |B| value is the absolute value of the B value.

[0208] The microcrystalline glass product of the present invention has the following properties:

[0209] 1) In some embodiments, the four-point bending strength of the glass-ceramic product with a thickness of 1 mm or less is 700 MPa or more, preferably 750 MPa or more, and more preferably 800 MPa or more. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, more preferably 0.5 to 0.8 mm, and even more preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.

[0210] 2) In some embodiments, the depth of the ion exchange layer of the microcrystalline glass product is 50 μm or more, preferably 60 μm or more, more preferably 80 μm or more, and further preferably 100 μm or more.

[0211] 3) In some embodiments, the drop ball test height of the glass-ceramic product with a thickness of 1 mm or less is 1100 mm or more, preferably 1300 mm or more, and more preferably 1500 mm or more. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, further preferably 0.5 to 0.8 mm, and further preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.

[0212] 4) In some embodiments, the Vickers hardness (H v ) is 750kgf / mm 2 Above, preferably 780kgf / mm 2 More preferably 800kgf / mm 2 More preferably, 810 kgf / mm 2 above.

[0213] 5) In some embodiments, the grain size of the microcrystalline glass product is 80 nm or less, preferably 60 nm or less, more preferably 50 nm or less, and even more preferably 40 nm or less.

[0214] 6) In some embodiments, the surface stress of the microcrystalline glass product is greater than 150 MPa, preferably greater than 170 MPa, and more preferably greater than 190 MPa.

[0215] 7) In some embodiments, the haze of the microcrystalline glass product with a thickness of 1 mm or less is 0.15% or less, preferably 0.12% or less, and more preferably 0.10% or less. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, further preferably 0.5 to 0.8 mm, and further preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.

[0216] 8) In some embodiments, the light transmittance of the microcrystalline glass product with a thickness of 1 mm or less at a wavelength of 550 nm is 88% or more, preferably 89% or more, more preferably 90% or more, and further preferably 91% or more. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, further preferably 0.5 to 0.8 mm, and further preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.

[0217] 9) In some embodiments, for a glass-ceramic product having a thickness of less than 1 mm, the average optical |B| value at 400-800 nm is less than 1.5, preferably less than 1.0, and more preferably less than 0.8. The thickness is preferably 0.2-1 mm, more preferably 0.3-0.9 mm, further preferably 0.5-0.8 mm, and further preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.

[0218] The microcrystalline glass of the present invention has the following properties:

[0219] 1) In some embodiments, the grain size of the glass-ceramics is 80 nm or less, preferably 60 nm or less, more preferably 50 nm or less, and further preferably 40 nm or less.

[0220] 2) In some embodiments, the haze of the microcrystalline glass with a thickness of 1 mm or less is 0.15% or less, preferably 0.12% or less, and more preferably 0.10% or less. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, further preferably 0.5 to 0.8 mm, and further preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.

[0221] 3) In some embodiments, the light transmittance of the microcrystalline glass with a thickness of 1 mm or less at a wavelength of 550 nm is 88% or more, preferably 89% or more, more preferably 90% or more, and further preferably 91% or more. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, further preferably 0.5 to 0.8 mm, and further preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.

[0222] 4) In some embodiments, the body ball drop height of the microcrystalline glass with a thickness of 1 mm or less is 1000 mm or more, preferably 1200 mm or more, and more preferably 1400 mm or more. The thickness is preferably 0.2 to 1 mm, more preferably 0.3 to 0.9 mm, further preferably 0.5 to 0.8 mm, and further preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.

[0223] 5) In some embodiments, for a glass-ceramic having a thickness of less than 1 mm, the average optical |B| value at 400-800 nm is less than 1.5, preferably less than 1.0, and more preferably less than 0.8. The thickness is preferably 0.2-1 mm, more preferably 0.3-0.9 mm, further preferably 0.5-0.8 mm, and further preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm, or 0.75 mm.

[0224] 6) In some embodiments, the Vickers hardness (H v ) is 650kgf / mm 2 Above, preferably 680kgf / mm 2 More preferably 700kgf / mm 2 above.

[0225] The microcrystalline glass, microcrystalline glass products, matrix glass, glass formed bodies, and microcrystalline glass formed bodies of the present invention can be widely made into glass cover plates or glass components due to the above-mentioned excellent properties; at the same time, the microcrystalline glass, microcrystalline glass products, matrix glass, glass formed bodies, and microcrystalline glass formed bodies of the present invention can be applied to electronic devices or display devices, such as mobile phones, watches, computers, touch screens, etc., for manufacturing protective glass for mobile phones, smart phones, tablet computers, laptops, PDAs, televisions, personal computers, MTA machines, or industrial displays, or for manufacturing touch screens, protective windows, car windows, train windows, aviation machinery windows, touch screen protective glass, or for manufacturing hard disk substrates or solar cell substrates, or for manufacturing white household appliances, such as for manufacturing refrigerator parts or kitchen utensils.

[0226] Example

[0227] In order to further clearly illustrate and describe the technical solution of the present invention, the following non-limiting examples are provided. The examples of the present invention have been tried hard to ensure the accuracy of the numerical values, but some errors and deviations must be taken into account. The composition of the microcrystalline glass or microcrystalline glass product is given in weight % based on the oxide and has been standardized to 100%.

[0228] <Glass-ceramic Example>

[0229] This embodiment adopts the above-mentioned method for manufacturing microcrystalline glass to obtain microcrystalline glass having the composition shown in Tables 1 to 3. In addition, the characteristics of each microcrystalline glass are measured by the test method described in the present invention, and the measurement results are shown in Tables 1 to 3. The thickness of the test sample used for the body drop ball height, haze, light transmittance, |B| value, etc. in the following embodiments is 0.7 mm.

[0230] Table 1.

[0231]

[0232]

[0233] Table 2.

[0234]

[0235]

[0236] Table 3.

[0237]

[0238]

[0239] <Glass-ceramic product example>

[0240] This embodiment adopts the manufacturing method of the above-mentioned microcrystalline glass products to obtain microcrystalline glass products with the compositions shown in Tables 4 to 6. In addition, the characteristics of each microcrystalline glass product are measured by the test method described in the present invention, and the measurement results are shown in Tables 4 to 6. The thickness of the test sample used for the four-point bending strength, drop ball test height, haze, light transmittance, |B| value, etc. in the following embodiments is 0.7 mm.

[0241] Table 4.

[0242]

[0243]

[0244] Table 5.

[0245]

[0246]

[0247] Table 6.

[0248]

[0249]

Claims

1. A glass-ceramic product, characterized in that: Its components, expressed in weight percentage, include: SiO2: 41-60%; Al2O3: 20-40%; Li2O: 2-15%; Na2O: 3-20%; P2O5+ZrO2: 1-15%.

2. The glass-ceramic product according to claim 1, characterized in that: Its components, expressed in weight percentage, also contain: K2O: 0-8%; and / or ZnO: 0-6%; and / or B2O3: 0-6%; and / or RO: 0-8%; and / or TiO2: 0-5%; and / or Ln2O3: 0-5%; and / or clarifier: 0-2%, wherein RO is one or more of MgO, CaO, SrO, and BaO, and Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

3. A glass-ceramic product, characterized in that: Its components include SiO2, Al2O3, Li2O and Na2O. The microcrystalline glass product contains a nepheline crystal phase. The surface stress of the microcrystalline glass product is above 150MPa.

4. A glass-ceramic product, characterized in that: Its components include SiO2, Al2O3, Li2O and Na2O. The four-point bending strength of microcrystalline glass products with a thickness of less than 1 mm is above 700 MPa.

5. A glass-ceramic product, characterized in that: Its components include SiO2, Al2O3, Li2O and Na2O, and the haze of microcrystalline glass products with a thickness of less than 1 mm is less than 0.15%.

6. A glass-ceramic product, characterized in that: The microcrystalline glass product contains a nepheline crystal phase, and the depth of the ion exchange layer is greater than 50 μm.

7. The glass-ceramic product according to any one of claims 3 to 6, characterized in that: Its components, expressed in weight percentage, contain: SiO2: 41-60%; and / or Al2O3: 20-40%; and / or Li2O: 2-15%; and / or Na2O: 3-20%; and / or P2O5+ZrO2: 1-15%; and / or K2O: 0-8%; and / or ZnO: 0-6%; and / or B2O3: 0-6%; and / or RO: 0-8%; and / or TiO2: 0-5%; and / or Ln2O3: 0-5%; and / or clarifier: 0-2%, wherein RO is one or more of MgO, CaO, SrO and BaO, and Ln2O3 is one or more of La2O3, Gd2O3 and Y2O3.

8. The glass-ceramic product according to any one of claims 1 to 6, characterized in that: The components are expressed in weight percentage, wherein: (Al2O3+Na2O) / P2O5 is 3.0-30.0, preferably (Al2O3+Na2O) / P2O5 is 4.0-20.0, more preferably (Al2O3+Na2O) / P2O5 is 5.0-15.0, and further preferably (Al2O3+Na2O) / P2O5 is 6.0-10.0; and / or SiO2 / Al2O3 is 1.2-2.8, preferably SiO2 / Al2O3 is 1.3-2.5, more preferably SiO2 / Al2O3 is 1.5-2.2, and further preferably SiO2 / Al2O3 is 1.6-2.0; and / or SiO 2 / (Na2O+B2O3) is 2.0 to 15.0, preferably SiO2 / (Na2O+B2O3) is 3.0 to 10.0, more preferably SiO2 / (Na2O+B2O3) is 4.0 to 8.0, and further preferably SiO2 / (Na2O+B2O3) is 5.0 to 7.0; and / or (Na2O+Li2O) / SiO2 is 0.1 to 0.8, preferably (Na2O+Li2O) / SiO2 is 0.15 to 0.7, more preferably (Na2O+Li2O) / SiO2 is 0.2 to 0.6, and further preferably (Na2O+Li2O) / SiO2 is 0.25 to 0.5; and / or (Na2O+Li2O) / SiO2 is 0.1 to 0.8, preferably (Na2O+Li2O) / SiO2 is 0.15 to 0.7, more preferably (Na2O+Li2O) / SiO2 is 0.2 to 0.6, and further preferably (Na2O+Li2O) / SiO2 is 0.25 to 0.5; (ZrO2+ZnO) / Na2O is 2.0 or less, preferably (ZrO2+ZnO) / Na2O is 1.5 or less, more preferably (ZrO2+ZnO) / Na2O is 0.01 to 1.0, and further preferably (ZrO2+ZnO) / Na2O is 0.1 to 0.5; and / or (P2O5+Na2O) / Li2O is 0.5 to 8.0, preferably (P2O5+Na2O) / Li2O is 0.8 to 5.0, more preferably (P2O5+Na2O) / Li2O is 1.0 to 3.0, and further preferably (P2O5+Na2O) / Li2O is 1.5 to 2.5; and / or (P2O5+Na2O) / Li2O is 0 .1 or above, preferably K2O / ZrO2 is 0.2-10.0, more preferably K2O / ZrO2 is 0.3-5.0, and further preferably K2O / ZrO2 is 0.4-1.5; and / or (ZnO+RO+B2O3+TiO2) / P2O5 is below 1.5, preferably (ZnO+RO+B2O3+TiO2) / P2O5 is below 1.0, more preferably (ZnO+RO+B2O3+TiO2) / P2O5 is below 0.5, and further preferably (ZnO+RO+B2O3+TiO2) / P2O5 is below 0.2, wherein RO is one or more of MgO, CaO, SrO, and BaO.

9. The glass-ceramic product according to any one of claims 1 to 6, characterized in that: Its components are expressed by weight percentage, wherein: SiO2: 43-55%, preferably SiO2: 46-53%; and / or Al2O3: 23-36%, preferably Al2O3: 25.5-32%; and / or Li2O: 3-13%, preferably Li2O: 5.5-11%; and / or Na2O: 5-15%, preferably Na2O: 6.5-12%; and / or P2O5+ZrO2: 2-12%, preferably P2O5+ZrO2: 4-10%; and / or K2O: 0-5%, preferably K2O: 0.1-3%; and / or Zn O: 0-3%, preferably ZnO: 0-1%; and / or B2O3: 0-3%, preferably B2O3: 0-1%; and / or RO: 0-5%, preferably RO: 0-2%; and / or TiO2: 0-3%, preferably TiO2: 0-1%; and / or Ln2O3: 0-3%, preferably Ln2O3: 0-1%; and / or clarifier: 0-1%, preferably clarifier: 0-0.5%, wherein RO is one or more of MgO, CaO, SrO, and BaO, and Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

10. The glass-ceramic product according to any one of claims 1 to 6, characterized in that: Its components are expressed in weight percentage, wherein: ZrO2: 0-6%, preferably ZrO2: 0-5%, more preferably ZrO2: 0.1-3%; and / or P2O5: 0-10%, preferably P2O5: 1-8%, more preferably P2O5: 2-6%.

11. The glass-ceramic product according to any one of claims 1 to 6, characterized in that: Its components, expressed in weight percentage, also contain: Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2+GeO2: 0-5%, preferably Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2+GeO2: 0-2%, more preferably Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2+GeO2: 0-1%.

12. The glass-ceramic product according to any one of claims 1 to 6, characterized in that: The microcrystalline glass product contains nepheline crystal phase; and / or lithium silicate crystal phase; and / or lithium phosphate crystal phase; and / or petalite crystal phase; and / or quartz crystal phase.

13. The glass-ceramic product according to any one of claims 1 to 6, characterized in that: The main crystal phase of the microcrystalline glass product is the nepheline crystal phase, or the microcrystalline glass product only contains the nepheline crystal phase.

14. The glass-ceramic product according to any one of claims 1 to 6, characterized in that: In the microcrystalline glass product, the weight percentage of the nepheline crystal phase in the microcrystalline glass product is 10-80%, preferably the weight percentage of the nepheline crystal phase in the microcrystalline glass product is 20-70%, and more preferably the weight percentage of the nepheline crystal phase in the microcrystalline glass product is 30-60%.

15. The glass-ceramic product according to any one of claims 1 to 6, characterized in that: The ion exchange layer depth of the microcrystalline glass product is 50 μm or more, preferably 60 μm or more, more preferably 80 μm or more, and further preferably 100 μm or more; and / or the Vickers hardness is 750 kgf / mm 2 Above, preferably 780kgf / mm 2 More preferably 800kgf / mm 2 More preferably, 810 kgf / mm 2 and / or a grain size of 80 nm or less, preferably 60 nm or less, more preferably 50 nm or less, and further preferably 40 nm or less; and / or a surface stress of 150 MPa or more, preferably 170 MPa or more, and more preferably 190 MPa or more.

16. The glass-ceramic product according to any one of claims 1 to 6, characterized in that: The microcrystalline glass products with a thickness of less than 1 mm have a four-point bending strength of more than 700 MPa, preferably more than 750 MPa, and more preferably more than 800 MPa; and / or the height of the falling ball test is more than 1100 mm, preferably more than 1300 mm, and more preferably more than 1500 mm; and / or the haze is less than 0.15%, preferably less than 0.12%, and more preferably less than 0.10%; and / or the light transmittance at a wavelength of 550 nm is more than 88%, preferably more than 89%, more preferably more than 90%, and further preferably more than 91%; and / or the average optical |B| value from 400 to 800 nm is less than 1.5, preferably less than 1.0, and more preferably less than 0.

8.

17. The glass-ceramic product according to claim 16, characterized in that: The thickness of the microcrystalline glass product is 0.2 to 1 mm, preferably 0.3 to 0.9 mm, more preferably 0.5 to 0.8 mm, and further preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm or 0.75 mm.

18. The glass-ceramic product according to any one of claims 1 to 6, characterized in that: Its components, expressed in weight percentage, also contain: NiO: 0-4%; and / or Ni2O3: 0-4%; and / or CoO: 0-2%; and / or Co2O3: 0-2%; and / or Fe2O3: 0-7%; and / or MnO2: 0-4%; and / or Er2O3: 0-8%; and / or Nd2O3: 0-8%; and / or Cu2O: 0-4%; and / or Pr2O3: 0-8%; and / or CeO2: 0-4%.

19. Glass-ceramics, characterized in that: Its components, expressed in weight percentage, include: SiO2: 41-60%; Al2O3: 20-40%; Li2O: 2-15%; Na2O: 3-20%; P2O5+ZrO2: 1-15%.

20. The glass-ceramic according to claim 19, characterized in that: Its components, expressed in weight percentage, also contain: K2O: 0-8%; and / or ZnO: 0-6%; and / or B2O3: 0-6%; and / or RO: 0-8%; and / or TiO2: 0-5%; and / or Ln2O3: 0-5%; and / or clarifier: 0-2%, wherein RO is one or more of MgO, CaO, SrO, and BaO, and Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

21. Glass-ceramics, characterized in that: The components thereof include SiO2, Al2O3, Li2O and Na2O, the microcrystalline glass contains a nepheline crystal phase, and the Vickers hardness of the microcrystalline glass is 650kgf / mm 2 above.

22. Glass-ceramics, characterized in that: Its components include SiO2, Al2O3, Li2O and Na2O, and the drop height of the microcrystalline glass with a thickness of less than 1 mm is more than 1000 mm.

23. Glass-ceramics, characterized in that: Its components include SiO2, Al2O3, Li2O and Na2O, and the haze of microcrystalline glass with a thickness of less than 1 mm is less than 0.15%.

24. Glass-ceramics, characterized in that: The transmittance of light at a wavelength of 550nm of microcrystalline glass with a thickness of less than 1mm containing nepheline crystal phase is over 88%.

25. The glass-ceramics according to any one of claims 21 to 24, characterized in that: Its components, expressed in weight percentage, contain: SiO2: 41-60%; and / or Al2O3: 20-40%; and / or Li2O: 2-15%; and / or Na2O: 3-20%; and / or P2O5+ZrO2: 1-15%; and / or K2O: 0-8%; and / or ZnO: 0-6%; and / or B2O3: 0-6%; and / or RO: 0-8%; and / or TiO2: 0-5%; and / or Ln2O3: 0-5%; and / or clarifier: 0-2%, wherein RO is one or more of MgO, CaO, SrO and BaO, and Ln2O3 is one or more of La2O3, Gd2O3 and Y2O3.

26. The glass-ceramics according to any one of claims 19 to 24, characterized in that: The components are expressed in weight percentage, wherein: (Al2O3+Na2O) / P2O5 is 3.0-30.0, preferably (Al2O3+Na2O) / P2O5 is 4.0-20.0, more preferably (Al2O3+Na2O) / P2O5 is 5.0-15.0, and further preferably (Al2O3+Na2O) / P2O5 is 6.0-10.0; and / or SiO2 / Al2O3 is 1.2-2.8, preferably SiO2 / Al2O3 is 1.3-2.5, more preferably SiO2 / Al2O3 is 1.5-2.2, and further preferably SiO2 / Al2O3 is 1.6-2.0; and / or SiO 2 / (Na2O+B2O3) is 2.0 to 15.0, preferably SiO2 / (Na2O+B2O3) is 3.0 to 10.0, more preferably SiO2 / (Na2O+B2O3) is 4.0 to 8.0, and further preferably SiO2 / (Na2O+B2O3) is 5.0 to 7.0; and / or (Na2O+Li2O) / SiO2 is 0.1 to 0.8, preferably (Na2O+Li2O) / SiO2 is 0.15 to 0.7, more preferably (Na2O+Li2O) / SiO2 is 0.2 to 0.6, and further preferably (Na2O+Li2O) / SiO2 is 0.25 to 0.5; and / or (Na2O+Li2O) / SiO2 is 0.1 to 0.8, preferably (Na2O+Li2O) / SiO2 is 0.15 to 0.7, more preferably (Na2O+Li2O) / SiO2 is 0.2 to 0.6, and further preferably (Na2O+Li2O) / SiO2 is 0.25 to 0.5; (ZrO2+ZnO) / Na2O is 2.0 or less, preferably (ZrO2+ZnO) / Na2O is 1.5 or less, more preferably (ZrO2+ZnO) / Na2O is 0.01 to 1.0, and further preferably (ZrO2+ZnO) / Na2O is 0.1 to 0.5; and / or (P2O5+Na2O) / Li2O is 0.5 to 8.0, preferably (P2O5+Na2O) / Li2O is 0.8 to 5.0, more preferably (P2O5+Na2O) / Li2O is 1.0 to 3.0, and further preferably (P2O5+Na2O) / Li2O is 1.5 to 2.5; and / or (P2O5+Na2O) / Li2O is 0 .1 or above, preferably K2O / ZrO2 is 0.2-10.0, more preferably K2O / ZrO2 is 0.3-5.0, and further preferably K2O / ZrO2 is 0.4-1.5; and / or (ZnO+RO+B2O3+TiO2) / P2O5 is below 1.5, preferably (ZnO+RO+B2O3+TiO2) / P2O5 is below 1.0, more preferably (ZnO+RO+B2O3+TiO2) / P2O5 is below 0.5, and further preferably (ZnO+RO+B2O3+TiO2) / P2O5 is below 0.2, wherein RO is one or more of MgO, CaO, SrO, and BaO.

27. The glass-ceramics according to any one of claims 19 to 24, characterized in that: Its components are expressed by weight percentage, wherein: SiO2: 43-55%, preferably SiO2: 46-53%; and / or Al2O3: 23-36%, preferably Al2O3: 25.5-32%; and / or Li2O: 3-13%, preferably Li2O: 5.5-11%; and / or Na2O: 5-15%, preferably Na2O: 6.5-12%; and / or P2O5+ZrO2: 2-12%, preferably P2O5+ZrO2: 4-10%; and / or K2O: 0-5%, preferably K2O: 0.1-3%; and / or Zn O: 0-3%, preferably ZnO: 0-1%; and / or B2O3: 0-3%, preferably B2O3: 0-1%; and / or RO: 0-5%, preferably RO: 0-2%; and / or TiO2: 0-3%, preferably TiO2: 0-1%; and / or Ln2O3: 0-3%, preferably Ln2O3: 0-1%; and / or clarifier: 0-1%, preferably clarifier: 0-0.5%, wherein RO is one or more of MgO, CaO, SrO, and BaO, and Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.

28. The glass-ceramics according to any one of claims 19 to 24, characterized in that: Its components are expressed in weight percentage, wherein: ZrO2: 0-6%, preferably ZrO2: 0-5%, more preferably ZrO2: 0.1-3%; and / or P2O5: 0-10%, preferably P2O5: 1-8%, more preferably P2O5: 2-6%.

29. The glass-ceramics according to any one of claims 19 to 24, characterized in that: Its components, expressed in weight percentage, also contain: Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2+GeO2: 0-5%, preferably Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2+GeO2: 0-2%, more preferably Yb2O3+Nb2O5+WO3+Bi2O3+Ta2O5+TeO2+GeO2: 0-1%.

30. The glass-ceramics according to any one of claims 19 to 24, characterized in that: The microcrystalline glass contains nepheline crystal phase; and / or lithium silicate crystal phase; and / or lithium phosphate crystal phase; and / or petalite crystal phase; and / or quartz crystal phase.

31. The glass-ceramics according to any one of claims 19 to 24, characterized in that: The main crystal phase of the microcrystalline glass is the nepheline crystal phase, or the microcrystalline glass only contains the nepheline crystal phase.

32. The glass-ceramics according to any one of claims 19 to 24, characterized in that: In the glass-ceramics, the weight percentage of the nepheline crystal phase in the glass-ceramics is 10-80%, preferably the weight percentage of the nepheline crystal phase in the glass-ceramics is 20-70%, and more preferably the weight percentage of the nepheline crystal phase in the glass-ceramics is 30-60%.

33. The glass-ceramics according to any one of claims 19 to 24, characterized in that: The crystal size of the microcrystalline glass is 80 nm or less, preferably 60 nm or less, more preferably 50 nm or less, and further preferably 40 nm or less; and / or the Vickers hardness is 650 kgf / mm 2 Above, preferably 680kgf / mm 2 More preferably 700kgf / mm 2 above.

34. The glass-ceramics according to any one of claims 19 to 24, characterized in that: For microcrystalline glass with a thickness of less than 1 mm, its main body ball drop height is more than 1000 mm, preferably more than 1200 mm, more preferably more than 1400 mm; and / or the haze is less than 0.15%, preferably less than 0.12%, more preferably less than 0.10%; and / or the light transmittance at a wavelength of 550 nm is more than 88%, preferably more than 89%, more preferably more than 90%, further preferably more than 91%; and / or the average light |B| value at 400 to 800 nm is less than 1.5, preferably less than 1.0, more preferably less than 0.

8.

35. The glass-ceramic according to claim 34, characterized in that: The thickness of the glass-ceramics is 0.2 to 1 mm, preferably 0.3 to 0.9 mm, more preferably 0.5 to 0.8 mm, and further preferably 0.55 mm, 0.6 mm, 0.68 mm, 0.7 mm or 0.75 mm.

36. The glass-ceramics according to any one of claims 19 to 24, characterized in that: Its components, expressed in weight percentage, also contain: NiO: 0-4%; and / or Ni2O3: 0-4%; and / or CoO: 0-2%; and / or Co2O3: 0-2%; and / or Fe2O3: 0-7%; and / or MnO2: 0-4%; and / or Er2O3: 0-8%; and / or Nd2O3: 0-8%; and / or Cu2O: 0-4%; and / or Pr2O3: 0-8%; and / or CeO2: 0-4%.

37. A glass cover plate, characterized in that: A glass-ceramic product comprising the glass-ceramic product according to any one of claims 1 to 18, and / or the glass-ceramic product according to any one of claims 19 to 36.

38. A glass component, characterized in that: A glass-ceramic product comprising the glass-ceramic product according to any one of claims 1 to 18, and / or the glass-ceramic product according to any one of claims 19 to 36.

39. A display device, characterized in that A microcrystalline glass product comprising any one of claims 1 to 18, and / or the microcrystalline glass according to any one of claims 19 to 36, and / or the glass cover plate according to claim 37, and / or the glass component according to claim 38.

40. An electronic device, characterized in that A microcrystalline glass product comprising any one of claims 1 to 18, and / or the microcrystalline glass according to any one of claims 19 to 36, and / or the glass cover plate according to claim 37, and / or the glass component according to claim 38.